Polishing composition
By using polishing compositions of silicate particles and other additives of 30 nm or greater average primary particle size, the shortcomings of Cu, Ta and TEOS material removal and topological correction effects in the existing CMP technology are solved, and efficient material removal and topological improvement are achieved.
Patent Information
- Application Number
- JP2024148252
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-09
AI Technical Summary
Existing chemical mechanical polishing (CMP) technologies are difficult to effectively remove materials such as copper (Cu), tantalum (Ta) and TEOS, especially in maintaining the integrity of Cu cross-connection and improving the topological correction of TEOS surface.
Silicate particles containing an average primary particle size of 30 nm or more are used as abrasives, combined with phosphate surfactants, corrosion inhibitors, water-soluble polymers and appropriate pH values (7-11) to form a highly efficient polishing composition.
The adjustable removal rate and high tantalum/TEOS removal rate selectivity for Cu, Ta and TEOS materials are achieved, which reduces the loss of copper intersection and effectively improves the topological correction effect of TEOS surface.
Smart Images

Figure 2025058928000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing composition. [Background technology]
[0002] The following discussion of the background of the present technology is provided merely as an aid in understanding the present technology and is not admitted to describe or constitute prior art to the present technology.
[0003] The following discussion of the background of the present technology is provided merely as an aid in understanding the present technology, and is not admitted to describe or constitute prior art to the present technology. One of the major chemical mechanical polishing (CMP) challenges for semiconductor manufacturing is the selective polishing of certain materials. Copper (Cu) is widely used as an interconnect material in semiconductor device fabrication, while tantalum (Ta), cobalt (Co) and combinations thereof are widely used as barrier materials, and SiO2 derived from tetraethyl orthosilicate (TEOS) is widely used as a substrate material. Herein, SiO2 derived from tetraethyl orthosilicate (TEOS) is also referred to simply as TEOS. Thus, tunable Cu, Ta, and TEOS removal rates are achieved, and high tantalum to TEOS removal rate (RR) selectivity (e.g., RR greater than about 1.2) is achieved. Ta / RR TEOS There is a need for chemical mechanical polishing compositions that provide high copper removal rates (e.g., less than about 200 Å / min) and minimize loss of Cu interconnects during the barrier polishing step. There is also a need for chemical mechanical polishing compositions and methods that provide good topography compensation in terms of dishing of Cu to TEOS. It is against this background that the polishing compositions and methods of the present disclosure have been developed. Summary of the Invention
[0004] In one aspect that may be combined with any other aspect or embodiment, the present disclosure relates to a polishing composition comprising: an abrasive containing silica particles having an average primary particle size of 30 nm or more; a phosphate surfactant; a corrosion inhibitor; and a water-soluble polymer; wherein the polishing composition has a pH of 7 to 11.
[0005] In some embodiments, the silica particles have an average primary particle size of 30 nm or more and 80 nm or less. In some embodiments, the abrasive is present in the polishing composition at a concentration of about 1.0 wt.% to about 5.0 wt.%. In some embodiments, the abrasive is present in the polishing composition at a concentration of about 2.0 wt.% to about 3.0 wt.%.
[0006] In some embodiments, the silica particles are surface-modified with a sulfonic acid.
[0007] In some embodiments, the silica particles have a D90 / D10 of greater than 1.3, hi some embodiments, the silica particles have a D90 / D10 of greater than 1.7.
[0008] In some embodiments, the phosphate surfactant comprises a polyoxyethylene alkyl phenyl ether phosphate or a polyoxyethylene alkenyl ether phosphate. In some embodiments, the phosphate surfactant comprises a polyoxyethylene alkyl phenyl ether phosphate having 5 to 16 oxyethylene units. In some embodiments, the phosphate surfactant comprises polyoxyethylene (7) nonyl phenyl phosphate.
[0009] In some embodiments, the phosphate surfactant is present in a concentration of 0.01% to 1.0% by weight, based on the total weight of the composition, hi some embodiments, the phosphate surfactant is present in a concentration of 0.005% to 0.3% by weight, based on the total weight of the composition.
[0010] In some embodiments, the corrosion inhibitor is a triazole. In some embodiments, the corrosion inhibitor comprises a benzotriazole.
[0011] In some embodiments, the corrosion inhibitor is present at a concentration of about 0.01% to about 0.20% by weight, hi some embodiments, the corrosion inhibitor is present at a concentration of about 0.05% to about 0.10% by weight.
[0012] In some embodiments, the water-soluble polymer is present at a concentration of about 0.01% to about 0.50% by weight, hi some embodiments, the water-soluble polymer is a polysaccharide present at a concentration of about 0.05% to about 0.10% by weight.
[0013] In some embodiments, the water soluble polymer is a polysaccharide, hi some embodiments, the water soluble polymer comprises pullulan.
[0014] In some embodiments, the polishing composition comprises an organic acid present at a concentration of about 0.01 wt % to about 0.50 wt %. In some embodiments, the organic acid comprises citric acid.
[0015] In some embodiments, the polishing composition comprises an electric conductivity controller. In some embodiments, the electric conductivity controller comprises tripotassium citrate.
[0016] In another aspect, which may be combined with any other aspect or embodiment, the present disclosure provides a method of polishing a substrate surface, the substrate surface comprising copper and TEOS, comprising the steps of: contacting the substrate surface with a polishing composition of any of the embodiments disclosed herein; moving a polishing pad relative to the substrate surface while contacting the polishing composition with the substrate surface; Including, the polishing step achieves a topography correction of 30 nm or more in terms of dishing of Cu on the TEOS surface; It concerns the method.
[0017] In some embodiments, the polishing step achieves a copper removal rate of 200 Å / min or less. In some embodiments, the polishing step achieves a copper removal rate of 150 Å / min or more. In some embodiments, the polishing step achieves a copper removal rate of 180 Å / min or more.
[0018] In some embodiments, the polishing step achieves a TEOS removal rate of 100 Å / min or greater, hi some embodiments, the polishing step achieves a TEOS removal rate of 110 Å / min or greater.
[0019] In some embodiments, the polishing step achieves a tantalum removal rate of 100 Å / min or greater. In some embodiments, the polishing step achieves a tantalum removal rate of 110 Å / min or greater. In some embodiments, the polishing step achieves a tantalum removal rate of 140 Å / min or greater.
[0020] In some embodiments, the polishing step achieves a Ta / TEOS polishing rate ratio of 1.00 or greater. In some embodiments, the polishing step achieves a Ta / TEOS polishing rate ratio of 1.20 or greater. In some embodiments, the polishing step achieves a Ta / TEOS polishing rate ratio of 1.30 or greater. [Brief description of the drawings]
[0021] [Figure 1A] Schematic (not to scale) of a Si wafer with a 3000 Å thermal oxide layer patterned with 1 μm trenches (A) with 9 μm trench-to-trench spacing (B), on which a 150 Å tantalum (Ta) barrier layer, and a 7000 Å copper (Cu) layer are deposited to replicate the interconnects. [Figure 1B] FIG. 1B is a schematic diagram of the patterned wafer of FIG. 1A after Cu polishing, leaving a Ta barrier layer across the entire wafer and patterned Cu interconnects in the trenches. [Figure 1C]FIG. 1C is a schematic diagram of an idealized surface topography after barrier layer polishing of the patterned wafer of FIG. 1B, where the tops of the Cu and Ta layers are approximately level with the top of the thermal oxide layer on the unpatterned portion of the wafer. [Figure 1D] Schematic of the non-ideal surface topography of the patterned wafer of FIG. 1B after barrier layer polishing, where the tops of the Cu and Ta layers are below the top of the thermal oxide layer on the unpatterned portion of the wafer. The amount of erosion is the height difference between the thermal oxide and the Cu or Ta layer. [Figure 1E] FIG. 1C is a schematic illustration of the non-ideal surface topography of the patterned wafer of FIG. 1B after barrier layer polishing, where the top of the Ta barrier layer is below the top of the thermal oxide layer on the non-patterned portion of the wafer (erosion) and the Cu layer protrudes above the top of the Ta barrier layer due to non-ideal Ta / Cu removal rate selectivity. [Figure 1F] FIG. 1C is a schematic illustration of the non-ideal surface topography of the patterned wafer of FIG. 1B after barrier layer polishing, where the top of the Cu layer (and optionally the top of the Ta layer) is below the top of the thermal oxide layer on the unpatterned and patterned portions of the wafer due to “dishing” of the Cu.
[0022] In the following, some specific embodiments contemplated by the present disclosure will be described in detail. Although various embodiments are described herein, it will be understood that it is not intended to limit the present technology to the described embodiments. On the contrary, it is intended to cover changes, modifications, and equivalents that may be included within the spirit and scope of the present technology as defined in the appended claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The present invention will be described in detail below. In this specification, "X to Y" means "X or more and Y or less", with the numerical values (X and Y) described before and after it being included as the lower and upper limits. When multiple "X to Y" are described, for example, when "X1 to Y1 or X2 to Y2" is described, the disclosure of each numerical value as the upper limit, the disclosure of each numerical value as the lower limit, and the combination of the upper and lower limits are all disclosed (that is, they are legal grounds for correction). Specifically, correction with X1 or more, correction with Y2 or less, correction with X1 or less, correction with Y2 or more, correction with X1 to X2, correction with X1 to Y2, etc. must all be considered legal. In addition, unless otherwise specified, the operation and measurement of physical properties are performed under the conditions of room temperature (20 to 25°C) / relative humidity 40 to 50% RH. In addition, the concentration described in this specification may be the concentration at POU (point of use) or the concentration before dilution to the POU concentration. The dilution ratio may be 2 to 10 times. It should be understood that all combinations of embodiments and explanations disclosed in this specification are disclosed in the present application. In other words, it should be understood that they can be the basis for amendment. In addition, when the content or concentration of each component is explained, if two or more kinds are included, it may be the total amount.
[0024] polishing composition In this specification, the polishing composition may also be referred to simply as the "composition."
[0025] The present disclosure relates to a polishing composition and method for improving topography correction and reducing dishing during chemical mechanical polishing (CMP) of a substrate (e.g., Si) having a barrier layer (e.g., Ta) and a metal layer (e.g., Cu interconnect) and a TEOS-derived SiO2 layer (i.e., a "TEOS substrate"). The polishing composition according to the present disclosure includes an abrasive containing silica particles having an average primary particle size of 30 nm or more; a phosphate surfactant; a corrosion inhibitor; and a water-soluble polymer, and has a pH of 7 to 11.
[0026] In some embodiments, a polishing composition is provided that includes: an abrasive containing silica particles having an average primary particle size of greater than 12 nm and / or an average secondary particle size of greater than 30 nm; a phosphate surfactant; a water-soluble polymer; and an electrical conductivity control agent; wherein the silica particles have a D90 / D50 ratio of greater than 1.3 or a D90 / D10 ratio of greater than 1.7 and / or are surface-modified with an organic acid, the phosphate surfactant contains 15 or less oxyethylene units and a linear or branched C4 or higher alkylphenyl, and is present at a concentration of less than 0.5 wt.% based on the total weight of the polishing composition, the electrical conductivity control agent is present at a concentration of less than 1 wt.% based on the total weight of the polishing composition, and the pH is greater than 8 and less than 11.
[0027] Abrasives The polishing composition according to the present disclosure comprises abrasive particles (i.e., "abrasive grains") suitable for polishing substrates including Cu, Ta, and one or more dielectric materials (e.g., BD, SiO2 (e.g., derived from TEOS), etc.). In some embodiments, the abrasive particles comprise one or more metal oxide particles, such as zirconia, hafnia, alumina, titania, silica, ceria, and any combination thereof. In some embodiments, the abrasive particles comprise colloidal silica, colloidal zirconia, or a combination thereof. In some embodiments, the abrasive particles comprise colloidal silica. Additionally, the abrasive particles may be commercial products, synthetic products, or any combination thereof. In some embodiments, the abrasive particles may be anionic. In the context of this application, "anionic" particles have a negative surface charge or a negative zeta potential at the pH of the polishing composition.
[0028] In some embodiments, the abrasive particles are surface-modified with a chemical species covalently attached to the particle surface and having a terminal anionic group. In some embodiments, the abrasive particles comprise colloidal particles that have been anionically modified, for example, by immobilization of an organic acid to the colloidal particle surface. In some embodiments, the terminal anionic group is a sulfonic acid group or a carboxy group.
[0029] In some embodiments, the immobilization of the organic acid on the surface of the abrasive particles (e.g., colloidal silica) of the polishing composition can be achieved by chemically bonding the functional group of the organic acid to the surface of the abrasive particles (e.g., colloidal silica). The immobilization of the organic acid on the colloidal silica cannot be achieved by simply allowing the colloidal silica and the organic acid to exist simultaneously. The immobilization of the organic acid (e.g., sulfonic acid) on the colloidal silica can be achieved, for example, by the method described in E.Cano-Serrano et al., Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups, CHEM.COMMUN., pp. 246-47 (2003), which is incorporated herein by reference in its entirety. Specifically, colloidal silica having a sulfonic acid immobilized on its surface can be obtained by coupling a silane coupling agent having a thiol group, such as 3-mercaptopropyltrimethoxysilane ("MPS"), to colloidal silica, followed by oxidation of the thiol group with hydrogen peroxide to form a surface-immobilized sulfonic acid (e.g., surface-bound propanesulfonic acid, e.g., oxidized MPS). Such silica abrasives are non-limiting examples of "sulfonic acid modified" abrasives.
[0030] Carboxylic acid can be immobilized on colloidal silica by, for example, the method described in Y. Kazuo et al., Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel, 3 CHEM.LETT., pp. 228-29 (2000), the entirety of which is incorporated herein by reference. Specifically, colloidal silica having carboxylic acid immobilized on its surface can be obtained by coupling a silane coupling agent containing a photoreactive 2-nitrobenzyl ester to colloidal silica, followed by photoirradiation. Such silica abrasives are non-limiting examples of "carboxylic acid modified" abrasives.
[0031] These examples of organic acid immobilization on colloidal silica are intended to be illustrative and not limiting. Other organic immobilization techniques using different organic acids and different abrasive particle materials (e.g., other than colloidal silica) are intended to be encompassed within the scope of this disclosure. In some embodiments, the silica particles are colloidal silica particles with organic acids (carboxylic acids) immobilized on the surface. In some embodiments, the silica particles are colloidal silica particles with organic acids (sulfonic acids) immobilized on the surface.
[0032] In some embodiments, the abrasive particles have an average primary particle size of about 30 nm or more, about 31 nm or more, about 32 nm or more, about 33 nm or more, about 34 nm or more, about 35 nm or more, about 36 nm or more, about 37 nm or more, about 38 nm or more, about 39 nm or more, about 40 nm or more, about 45 nm or more, about 50 nm or more, about 55 nm or more, about 60 nm or more, about 65 nm or more, about 70 nm or more, about 75 nm or more, about 80 nm or more, about 85 nm or more, about 90 nm or more, about 95 nm or more, about 100 nm or more, about 110 nm or more, about 120 nm or more, about 130 nm or more, about 140 nm or more, about 150 nm or more, or any range or value therebetween. In some embodiments, the abrasive particles have an average primary particle size of greater than 12 nm, 13 nm or more, 15 nm or more, 17 nm or more, 19 nm or more, 21 nm or more, 23 nm or more, 25 nm or more, 29 nm or more, 30 nm or more, or any range or value therebetween.
[0033] The average primary particle size of the abrasive grains can be measured using a field emission scanning electron microscope (FE-SEM). Manufacturer and model number: S-4800 (Hitachi High-Technologies Corporation).
[0034] Here, ranges can be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, another embodiment includes from the one particular value and / or to the other particular value. Similarly, when values are expressed as approximations, by using the antecedent "about," it will be understood that the particular value forms another embodiment. It will further be understood that the endpoints of each range are significant in relation to the other endpoint, and independently of the other endpoint. It will also be understood that there are a number of values disclosed herein, and that each value is herein disclosed as "about" that particular value, in addition to the value itself. For example, if the value "10" is disclosed, then "about 10" is also disclosed. It will also be understood that each unit between two particular units is also disclosed. For example, if 10 and 15 are disclosed, then 11, 12, 13, and 14 are also disclosed. In this specification, about X (X is a numerical value) may mean that it further includes ±10% or ±5% of X, and for example, ±10% means X×0.9 to X×1.1. In addition, about X may be X itself.
[0035] In some embodiments, the abrasive particles have an average primary particle size of about 150 nm or less, about 140 nm or less, about 130 nm or less, about 120 nm or less, about 110 nm or less, about 100 nm or less, about 95 nm or less, about 90 nm or less, about 85 nm or less, about 80 nm or less, about 75 nm or less, about 70 nm or less, about 65 nm or less, about 60 nm or less, about 55 nm or less, about 50 nm or less, about 49 nm or less, about 48 nm or less, about 47 nm or less, about 46 nm or less, about 45 nm or less, about 44 nm or less, about 43 nm or less, about 42 nm or less, about 41 nm or less, about 40 nm or less, about 39 nm or less, about 38 nm or less, about 37 nm or less, about 36 nm or less, about 35 nm or less, or any range or value therebetween.
[0036] In some embodiments, the abrasive particles may have a diameter of about 30 nm to about 150 nm, about 30 nm to about 100 nm, about 30 nm to about 90 nm, about 30 nm to about 80 nm, about 30 nm to about 70 nm, about 30 nm to about 60 nm, about 30 nm to about 50 nm, about 30 nm to about 45 nm, about 30 nm to about 40 nm, about 30 nm to about 35 nm, greater than 30 nm to about 150 nm, greater than 30 nm to about 100 nm, greater than 30 nm to about 90 nm, greater than 30 nm to about 80 nm, greater than 30 nm to about 70 nm, greater than 30 nm to about 60 nm, greater than 30 nm to about 50 nm, greater than 30 nm to about 45 nm, greater than 30 nm to about 40 nm, greater than 30 nm to about 35 nm, greater than 30 nm to about 150 nm, greater than 30 nm to about 100 nm, greater than 30 nm to about 90 nm, greater than 30 nm to about 80 nm, greater than 30 nm to about 70 nm, greater than 30 nm to about 60 nm, greater than 30 nm to about 50 nm, greater than 30 nm to about 50 nm, greater than 30 nm to about 60 nm, greater than 30 nm to about 150 nm, greater than 30 nm to about 100 nm, greater than 30 nm to about 90 nm, greater than 30 nm to about 80 nm, greater than 30 nm to about 70 nm, greater than 30 nm to about 60 nm, greater than 30 nm to about 150 nm, greater than 30 nm to about 100 nm, greater than 30 nm to about 90 nm, greater than ~50nm, more than 30nm~45nm, more than 30nm~40nm, more than 30nm~35nm, 32nm~150nm, 32nm~100nm, 32nm~90nm, 32nm~80nm, 32nm~70nm, 32nm~ Approximately 60 nm, approximately 32 nm to approximately 50 nm, approximately 32 nm to approximately 45 nm, approximately 32 nm to approximately 40 nm, approximately 32 nm to approximately 35 nm, approximately 35 nm to approximately 150 nm, approximately 35 nm to approximately 100 nm, approximately 35 nm to approximately 90 nm, approximately 35 nm to approximately 80 nm, approximately 35 nm to approximately 70nm, approximately 35nm to approximately 60nm, approximately 35nm to approximately 50nm, approximately 35nm to approximately 45nm, approximately 35nm to approximately 40nm, approximately 40nm to approximately 150nm, approximately 40nm to approximately 100nm, approximately 40nm to approximately 90nm, approximately 40nm to approximately 80nm, approximately 40nm to approximately 7 0nm, about 40nm to about 60nm, about 40nm to about 50nm, about 40nm to about 45nm, about 45nm to about 150nm, about 45nm to about 100nm, about 45nm to about 90nm, about 45nm to about 80nm, about 45nm to about 70nm, about 45nm to about 60 nm, about 45 nm to about 50 nm, about 50 nm to about 150 nm, about 50 nm to about 100 nm, about 50 nm to about 90 nm, about 50 nm to about 800 nm, about 50 nm to about 70 nm, about 50 nm to about 60 nm, about 60 nm to about 150 nm, about 60 nm to about 100 nm, about 60 nm to about 90 nm, about 60 nm to about 80 nm, about 60 nm to about 70 nm, about 70 nm to about 100 nm, about 70 nm to about 90 nm, about 70 nm to about 80 nm, or any range or value therein. In some embodiments, the abrasive particles have an average primary particle diameter of 15 to 35 nm. In some embodiments, the abrasive particles have an average primary particle diameter of less than 78 nm.
[0037] In some embodiments, the abrasive particles have an average secondary particle size of about 50 nm or more, about 51 nm or more, about 52 nm or more, about 53 nm or more, about 54 nm or more, about 55 nm or more, about 56 nm or more, about 57 nm or more, about 58 nm or more, about 59 nm or more, about 60 nm or more, about 61 nm or more, about 62 nm or more, about 63 nm or more, about 64 nm or more, about 65 nm or more, about 66 nm or more, about 67 nm or more, about 68 nm or more, about 69 nm or more, about 70 nm or more, about 75 nm or more, about 80 nm or more, about 85 nm or more, about 90 nm or more, about 95 nm or more, about 100 nm or more, about 110 nm or more, about 120 nm or more, about 130 nm or more, about 140 nm or more, about 150 nm or more, or any range or value therebetween. In some embodiments, the abrasive particles have an average secondary particle size of greater than 30 nm, 35 nm or more, 40 nm or more, 45 nm or more, or any range or value therebetween. A particle size distribution measuring device (Horiba particle size distribution device) can measure the average secondary particle size of the abrasive particles.
[0038] In some embodiments, the abrasive particles have an average secondary particle size of about 150 nm or less, about 140 nm or less, about 130 nm or less, about 120 nm or less, about 110 nm or less, about 100 nm or less, about 95 nm or less, about 90 nm or less, about 85 nm or less, about 80 nm or less, about 75 nm or less, about 70 nm or less, about 65 nm or less, about 60 nm or less, about 55 nm or less, or any range or value therebetween. In some embodiments, the abrasive particles have an average secondary particle size of less than 120 nm.
[0039] In some embodiments, the abrasive particles have an average secondary particle size of about 50 nm to about 150 nm, about 50 nm to about 100 nm, about 50 nm to about 90 nm, about 50 nm to about 80 nm, about 50 nm to about 70 nm, about 50 nm to about 60 nm, about 60 nm to about 150 nm, about 60 nm to about 100 nm, about 60 nm to about 90 nm, about 60 nm to about 80 nm, about 60 nm to about 70 nm, about 70 nm to about 150 nm, about 70 nm to about 100 nm, about 70 nm to about 90 nm, about 70 nm to about 80 nm, about 80 nm to about 150 nm, about 80 nm to about 100 nm, about 80 nm to about 90 nm, or any range or value therein.
[0040] In some embodiments, the abrasive particles comprise about 0.1 wt.% or more, about 0.15 wt.% or more, about 0.2 wt.% or more, about 0.25 wt.% or more, about 0.3 wt.% or more, about 0.35 wt.% or more, about 0.4 wt.% or more, about 0.45 wt.% or more, about 0.5 wt.% or more, about 0.55 wt.% or more, about 0.60 wt.% or more, about 0.65 wt.% or more, about 0.7 wt.% or more, about 0.75 wt.% or more, about 0.8 wt.% or more, about 0.85 wt.% or more, about 0.9 wt.% or more, about 0.95 wt.% or more, about 1.0 wt.% or more, about 1.1 wt.% or more, about 1.2 wt.% or more, about 1.3 wt.% or more, about 1.4 wt.% or more, about 1.5 wt.% or more, about 1.
[0043] The composition is present in a concentration by weight of 6% by weight or more, about 1.7% by weight or more, about 1.8% by weight or more, about 1.9% by weight or more, about 2.0% by weight or more, about 2.1% by weight or more, about 2.2% by weight or more, about 2.3% by weight or more, about 2.4% by weight or more, about 2.5% by weight or more, about 3.0% by weight or more, about 3.5% by weight or more, about 4.0% by weight or more, about 4.5% by weight or more, about 5.0% by weight or more, about 5.5% by weight or more, about 6.0% by weight or more, about 6.5% by weight or more, about 7.0% by weight or more, about 7.5% by weight or more, about 8.0% by weight or more, about 8.5% by weight or more, about 9.0% by weight or more, about 9.5% by weight or more, about 10.0% by weight or more, or any range or value therebetween. In some embodiments, the abrasive particles are present in the composition at a concentration by weight of about 0.01% by weight or more, about 0.05% by weight or more, or any range or value therebetween, based on the total weight of the composition.
[0041] The terms "D10", "D50", and "D90" refer to the particle size distribution parameters of the abrasive particles (or abrasive grains) disclosed herein. As used herein, the term "D10" refers to the cumulative 10% particle size (e.g., diameter) counted from the minimum particle size in a particle size distribution histogram. That is, D10 is the particle size at which 10% of the particles in the particle size distribution have a smaller size and 90% have a larger size. Similarly, as used herein, the term "D50" refers to the cumulative 50% particle size (e.g., diameter) counted from the minimum particle size in a particle size distribution histogram. That is, D50 is the particle size at which 50% of the particles in the particle size distribution have a smaller size and 50% have a larger size. Similarly, "D90" refers to the cumulative 90% particle size (e.g., diameter) counted from the minimum particle size in a particle size distribution histogram. That is, D90 is the particle size at which 90% of the particles in a particle size distribution have a smaller size and 10% have a larger size. "D10", "D50", and "D90" can all be measured with a Malvern Panalytical Zetasizer Nano Light Scattering System.
[0042] The abrasive particles may have any suitable D90 / D50 ratio to achieve good topography compensation and Cu, Ta, and TEOS removal rates. In some embodiments, the abrasive particles have a D90 / D50 ratio of at least about 1.2, at least about 1.3, at least about 1.4, at least about 1.5, at least about 1.6, at least about 1.7, at least about 1.8, or at least about 1.9. Alternatively, or in addition, in some embodiments, the abrasive particles have a D90 / D50 ratio of about 4.0 or less, about 3.5 or less, about 3.0 or less, about 2.5 or less, about 2.4 or less, about 2.3 or less, about 2.2 or less, about 2.1 or less, about 2.0 or less, about 1.9 or less, about 1.8 or less, about 1.7 or less, about 1.6 or less, about 1.5 or less, or any range or value therebetween. In some embodiments, the abrasive particles have a D90 / D50 ratio of greater than 1.3.
[0043] In some embodiments, when the silica particles are not surface-modified with an organic acid, the silica particles have a D90 / D50 ratio of less than 1.9.
[0044] The abrasive particles may have any suitable D90 / D10 ratio to achieve good topography compensation and Cu, Ta, and TEOS removal rates. In some embodiments, the abrasive particles have a D90 / D10 ratio of at least about 1.2, at least about 1.3, at least about 1.4, at least about 1.5, at least about 1.6, at least about 1.7, at least about 1.8, at least about 1.9, at least about 2.0, at least about 2.1, at least about 2.2, at least about 2.3, at least about 2.4, at least about 2.5, at least about 2.6, at least about 2.7, at least about 2.8, at least about 2.9, or at least about 3.0. Alternatively, or in addition, in some embodiments, the abrasive particles have a D90 / D10 ratio of about 3.5 or less, about 3.4 or less, about 3.3 or less, about 3.2 or less, about 3.1 or less, about 3.0 or less, about 2.9 or less, about 2.8 or less, about 2.7 or less, about 2.6 or less, about 2.5 or less, about 2.4 or less, about 2.3 or less, about 2.2 or less, about 2.1 or less, about 2.0 or less, about 1.9 or less, about 1.8 or less, about 1.7 or less, about 1.6 or less, about 1.5 or less, or any range or value therebetween. In some embodiments, the abrasive particles have a D90 / D10 ratio of greater than 1.7.
[0045] In some embodiments, the abrasive particles are about 10.0 wt.% or less, about 9.5 wt.% or less, about 9.0 wt.% or less, about 8.5 wt.% or less, about 8.0 wt.% or less, about 7.5 wt.% or less, about 7.0 wt.% or less, about 6.5 wt.% or less, about 6.0 wt.% or less, about 5.5 wt.% or less, about 5.0 wt.% or less, about 4.5 wt.% or less, about 4.0 wt.% or less, about 3.9 wt.% or less, based on the total weight of the composition. , about 3.8% by weight or less, about 3.7% by weight or less, about 3.6% by weight or less, about 3.5% by weight or less, about 3.4% by weight or less, about 3.3% by weight or less, about 3.2% by weight or less, about 3.1% by weight or less, about 3.0% by weight or less amount% or less, about 2.9% by weight or less, about 2.8% by weight or less, about 2.7% by weight or less, about 2.6% by weight or less, about 2.5% by weight or less, about 2.4% by weight or less, about 2.3% by weight or less, about 2.2% by weight or less, about 2 .1% by weight or less, about 2.0% by weight or less, about 1.9% by weight or less, about 1.8% by weight or less, about 1.7% by weight or less, about 1.6% by weight or less, about 1.5% by weight or less, about 1.4% by weight or less, about 1.3% by weight or less Lower, about 1.2% by weight or less, about 1.1% by weight or less, about 1.0% by weight or less, about 0.95% by weight or less, about 0.9% by weight or less, about 0.85% by weight or less, about 0.8% by weight or less, about 0.75% by weight or less, about Present in the composition at a concentration by weight of 0.7% by weight or less, about 0.65% by weight or less, about 0.6% by weight or less, about 0.55% by weight or less, about 0.5% by weight or less, about 0.45% by weight or less, about 0.4% by weight or less, about 0.35% by weight or less, about 0.3% by weight or less, about 0.25% by weight or less, about 0.2% by weight or less, about 0.15% by weight or less, about 0.1% by weight or less, or any range or value therebetween.
[0046] In some embodiments, the abrasive particles are present in an amount of from about 0.1% to about 10.0% by weight, from about 0.2% to about 10.0% by weight, from about 0.3% to about 10.0% by weight, from about 0.4% to about 10.0% by weight, from about 0.5% to about 10.0% by weight, from about 0.6% to about 10.0% by weight, from about 0.7% to about 10.0% by weight, from about 0.8% to about 10.0% by weight, from about 0.9% to about 10.0% by weight, from about 1.0% to about 10.0% by weight, from about 2% to about 10.0% by weight, from about 2.2% to about 10.0% by weight, from about 2.5% to about 10.0% by weight, based on the total weight of the composition. %, about 2.8% to about 10.0%, about 3% to about 10.0%, about 3.5% to about 10.0%, about 4% to about 10.0%, about 5% to about 10.0%, about 0.1% to about 5%, about 0.2% to about 5%, about 0.3% to about 5%, about 0 .4% to 5% by weight, 0.5% to 5%, 0.6% to 5%, 0.7% to 5%, 0.8% to 5%, 0.9% to 5%, 1.0% to 5%, 1.5% to 5%, 2.0% to 5%, approx. 2.2% to about 5% by weight, about 2.5% to about 5% by weight, about 3.0% to about 5% by weight, about 0.1% to about 3.0% by weight, about 0.2% to about 3.0% by weight, about 0.3% to about 3.0% by weight, about 0.4% to about 3.0% by weight, about 0.5% to about 3.0% by weight, about 0.6 Weight% to about 3.0% by weight, about 0.7% to about 3.0% by weight, about 0.8% to about 3.0% by weight, about 0.9% to about 3.0% by weight, about 1.0% to about 3.0% by weight, about 1.2% to about 3.0% by weight, about 1.5% to about 3.0% by weight, about 1.8% to about 3.0% by weight, approx. 2.0% to about 3.0% by weight, about 2.2% to about 3.0% by weight, about 2.2% to about 2.5% by weight, about 0.1% to about 2.5% by weight, about 0.2% to about 2.5% by weight, about 0.3% to about 2.5% by weight, about 0.4% to about 2.5% by weight, about 0.5% to about 2.5% by weight %, about 0.6% to about 2.5%, about 0.7% to about 2.5%, about 0.8% to about 2.5%, about 0.9% to about 2.5%, about 1.0% to about 2.5%, about 1.2% to about 2.5%, about 1.5% to about 2.5%, about 1.8% to about 2.5% by weight, about 2.0% by weight to about 2.5% by weight, or any range or value therein.
[0047] In some embodiments, the abrasive particles (e.g., colloidal silica or anionically modified colloidal silica) have a negative charge under the pH conditions used in the polishing composition of the present disclosure. In some embodiments, the abrasive particles (e.g., colloidal silica or anionically modified colloidal silica) have a negative charge at the pH of the polishing composition (e.g., 6.5 to 11, or 7 to 11). In some embodiments, the zeta potential of the abrasive particles is negative by more than -1 mV, -2 mV, -5 mV, -10 mV, -15 mV, -20 mV, -25 mV, -30 mV, -35 mV, or -40 mV, or any range or value therebetween. In some embodiments, the zeta potential of the abrasive particles is -40 mV to -5 mV, -40 mV to -10 mV, -40 mV to -15 mV, -40 mV to -20 mV, -40 mV to -25 mV, or -40 mV to -35 mV at the pH of the polishing composition (e.g., 6.5 to 11, or 7 to 11). In some embodiments, the zeta potential of the anionic modified abrasive particles is more negatively charged (i.e., more negative) than the corresponding unmodified abrasive particles (e.g., unmodified colloidal silica) at the same pH conditions.
[0048] In some embodiments, the abrasive particles substantially comprise colloidal silica. As used herein, "substantially" means that 95% by weight or more, preferably 98% by weight or more, more preferably 99% by weight or more of the particles constituting the abrasive are colloidal silica, including 100% by weight of the particles being colloidal silica. In some embodiments, the colloidal silica has an organic acid immobilized on its surface. In some embodiments, the colloidal silica has a sulfonic acid immobilized on its surface.
[0049] The silanol group density of the abrasive particles can vary. 2 " and the unit is "nm -2" can also be written.
[0050] The average silanol group density on the surface of the abrasive particles is 6.7 nm -2 Below, 6.6nm -2 Below, 6.5nm -2 Below, 6.4nm -2 Below, 6.3nm -2 Below, 6.2nm -2 Below, 6.1nm -2 Below, 6.0nm -2 Below, 5.9nm -2 Less than or equal to 5.8 nm -2 The average silanol group density on the surface of the abrasive particle is 1.0 nm or less. -2 Above, 2.0nm -2 Above, 3.0nm -2 Above, 4.0nm -2 Above, 5.0nm -2 Above, 5.2nm -2 That's it, 5.4 nm -2 Above, 5.6nm -2 Above, 5.8nm -2 or more than 6.0 nm -2 That's all.
[0051] The lower limit of the average silanol group density is generally zero.
[0052] The number of silanol groups per unit surface area of the abrasive particles can be calculated by the Sears method using neutralization titration as described in "Determination of Specific Surface Area of Colloidal Silica by Titration with Sodium Hydroxide" by GW Sears, Analytical Chemistry, 1956, Vol. 28 (No. 12), pp. 1982-1983. The calculation formula for the number of silanol groups is as follows:
[0053] ρ = (c × a × N A ) / (C×S) ρ: Number of silanol groups [pcs / nm 2 ] c: Concentration of the sodium hydroxide solution used in the titration [mol / L] a: Amount of sodium hydroxide solution with a pH of 4 to 9 to be dripped [ml] N A :Avogadro's number (6.022 x 10 23 [pieces / mol]) C: Mass of abrasive particles (silica) [g] S:BET specific surface area [nm 2 / g] The number of silanol groups per unit surface area of the abrasive particle can be controlled by selecting the manufacturing method of the abrasive grains.
[0054] Surfactants Anionic (e.g., phosphate) surfactants In some embodiments, the polishing composition according to the present disclosure comprises one or more anionic surfactants (e.g., phosphate surfactants). As a non-limiting example, in some embodiments, the anionic surfactant comprises a polyoxyethylene alkyl ether phosphate or a polyoxyethylene alkenyl ether phosphate. In some embodiments, the polyoxyethylene alkyl ether phosphate may comprise a monoester phosphate, a diester phosphate, or a mixture of the two. In some embodiments, the polyoxyethylene alkyl ether phosphate has the following structure: [(alkyl chain)-(polyethylene oxide)-O] m -phosphate, where m is 1 or 2 or 3. In some embodiments, the polyoxyethylene alkyl ether phosphate has the following formula (I): [Tail-(OC2H5) n -O] m -PO q H r (I) (wherein (OCH) is an "EO group" and n is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or 16. In some embodiments, the number of EO groups is 10 or less. In some embodiments, m is 1, 2, or 3. In some embodiments, r is 0, 1, or 2. In some embodiments, q is 1, 2, or 3.
[0055] In some embodiments, the phosphate surfactant comprises a polyoxyethylene alkyl phenyl ether phosphate. In some embodiments, the phosphate surfactant comprises a polyoxyethylene alkyl phenyl ether phosphate having 5 to 16 oxyethylene units. In some embodiments, the phosphate surfactant comprises a polyoxyethylene alkyl phenyl ether phosphate having 1 to 15, 2 to 14, 3 to 13, 4 to 12, 5 to 11, 6 to 10, or 6 to 9 oxyethylene units. In some embodiments, the number of carbon atoms in the alkyl in the polyoxyethylene alkyl phenyl ether phosphate is 4 to 18, 5 to 17, 6 to 16, 7 to 15, 8 to 14, 8 to 13, 8 to 12, or 8 to 11.
[0056] In some embodiments, (m, q, r) is (1, 3, 2), (2, 2, 1), or (3, 1, 0). In some embodiments, n is independently selected at each occurrence from the group of 1, 2, 3, 4, 5, 6, 7, 8, or 9. In some embodiments, (m, q, r) is (1, 3, 2). In some embodiments, (m, q, r) is (2, 2, 1). In some embodiments, (m, q, r) is (3, 1, 0). In some embodiments, (m, q, r) is a combination of (1, 3, 2), (2, 2, 1), and (3, 1, 0).
[0057] In some embodiments, the tail portion is a substituted or unsubstituted straight chain or branched alkyl, alkenyl, alkynyl, phenyl, or alkylphenyl C 2~24In some embodiments, the alkyl tail comprises a phenyl group (styrenated phenyl or nonylphenyl). In some embodiments, the tail comprises a hydrocarbon having at least 2, at least 3, at least 4, at least 5, at least 6, at least 7, at least 8, at least 9, at least 10, at least 11, at least 12, at least 13, at least 14, at least 15, at least 16, at least 17, at least 18, at least 19, at least 20, at least 21, at least 22, at least 23, at least 24, or more carbon atoms.
[0058] In some embodiments, the phosphate surfactant comprises 15 or fewer oxyethylene units and a linear or branched C4 or higher alkylphenyl, and is present at a concentration of less than 0.5 wt. %, based on the total weight of the polishing composition.
[0059] In some embodiments, the number of oxyethylene units is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. In some embodiments, the number of oxyethylene units is 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15.
[0060] In some embodiments, the alkyl in the alkylphenyl is linear or branched, C4 or more, C5 or more, C6 or more, C7 or more, C8 or more, C9 or more, C 10 The above, or C 11 In some embodiments, the alkyl in the alkylphenyl is a straight or branched C 18 Below, C 17 Below, C 16 Below, C 15 Below, C 14 Below, C 13 Below, C 12 Below, C 11 Below, or C 10 The following is the result.
[0061] In some embodiments, the phosphate surfactant has the following formula (I): [Tail-(OC2H5) n -O] m -PO q H r (I) wherein n is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15; (m, q, r) are (1, 3, 2), (2, 2, 1), or (3, 1, 0); and the tail is a C4 or higher alkylphenyl. In some embodiments, the tail is a C7 or higher, C8 or higher, C9 or higher, C 10 The above, or C 11 In some embodiments, the tail is C 18 Below, C 17 Below, C 16 Below, C 15 Below, C 14 Below, C 13 Below, C 12 Below, C 11 Below, or C 10 The following alkylphenyl:
[0062] In some embodiments, the tail is C5-C 11 is an alkylphenyl.
[0063] In some embodiments, n is 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15. In some embodiments, n is 6, 7, 8, or 9.
[0064] In some embodiments, 80% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, or 99% by weight or more of the surfactants present in the polishing composition are made up of the phosphate surfactant represented by formula (I).
[0065] In some embodiments, the phosphate surfactant has a molecular weight of about 150 g / mol or more, about 200 g / mol or more, about 250 g / mol or more, about 300 g / mol or more, about 350 g / mol or more, about 400 g / mol or more, about 450 g / mol or more, about 500 g / mol or more, about 550 g / mol or more, about 600 g / mol or more, about 650 g / mol or more, about 700 g / mol or more, about 750 g / mol or more, about 800 g / mol or more, about 850 g / mol or more, about 900 g / mol or more, about 950 g / mol or more, about 1000 g / mol or more, about 1100 g / mol or more, about 1200 g / mol or more, about 1300 g / mol or more, about 1400 g / mol or more, about 1500 g / mol or more, or any range or value therebetween.
[0066] In some embodiments, the phosphate surfactant comprises at least one of laureth-4 phosphate (e.g., Ethfac 142W), polyoxyethylene (5) nonylphenyl phosphate, polyoxyethylene (7) nonylphenyl phosphate (e.g., Ethfac NP-110), polyoxyethylene (10) nonylphenyl phosphate, polyoxyethylene (12) nonylphenyl phosphate, polyoxyethylene (16) nonylphenyl phosphate, polyoxyethylene (7) phenyl phosphate, polyoxyethylene (7) dodecylphenyl phosphate, polyoxyethylene (7) nonyl phosphate, polyoxyethylene (7) propylphenyl phosphate, and polyoxyethylene (10) oleyl ether phosphate (e.g., Crodafos O10A), and combinations thereof. In some embodiments, the phosphate surfactant comprises polyoxyethylene (7) nonylphenyl phosphate (e.g., Ethfac NP-110) or polyoxyethylene (10) nonylphenyl phosphate. In some embodiments, the phosphate surfactant comprises polyoxyethylene (7) nonylphenyl phosphate (e.g., Ethfac NP-110).
[0067] In some embodiments, the anionic surfactant (e.g., phosphate surfactant) is about 0.001 wt % or more, about 0.002 wt % or more, about 0.003 wt % or more, about 0.004 wt % or more, about 0.005 wt % or more, about 0.006 wt % or more, about 0.007 wt % or more, about 0.008 wt % or more, about 0.009 wt % or more, about 0.01 wt % or more, about 0.02 wt % or more, about 0.03 wt % or more, about 0.04 wt % or more, about 0.05 wt % or more, about 0.06 wt % or more, about 0. ...8 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, about 0.08 wt % or more, The composition is present in a concentration by weight of 0.04% by weight or more, about 0.05% by weight or more, about 0.06% by weight or more, about 0.07% by weight or more, about 0.08% by weight or more, about 0.09% by weight or more, about 0.1% by weight or more, about 0.2% by weight or more, about 0.3% by weight or more, about 0.4% by weight or more, about 0.5% by weight or more, about 0.6% by weight or more, about 0.7% by weight or more, about 0.8% by weight or more, about 0.9% by weight or more, about 1.0% by weight or more, or any range or value therebetween. In some embodiments, the anionic surfactant (e.g., phosphate surfactant) is present in a concentration by weight of greater than 0.01% and less than 0.1% by weight, based on the total weight of the polishing composition.
[0068] In some embodiments, the anionic surfactant (e.g., phosphate surfactant) is about 1.0 wt. % or less, about 0.9 wt. % or less, about 0.8 wt. % or less, about 0.7 wt. % or less, about 0.6 wt. % or less, about 0.5 wt. % or less, about 0.4 wt. % or less, about 0.3 wt. % or less, about 0.2 wt. % or less, about 0.1 wt. % or less, about 0.09 wt. % or less, about 0.08 wt. % or less, based on the total weight of the polishing composition. The anionic surfactant (e.g., phosphate surfactant) is present in the composition at a concentration by weight of less than 0.5 wt.%, about 0.07 wt.% or less, about 0.06 wt.% or less, about 0.05 wt.% or less, about 0.04 wt.% or less, about 0.03 wt.% or less, about 0.02 wt.% or less, about 0.01 wt.% or less, about 0.009 wt.% or less, about 0.008 wt.% or less, about 0.007 wt.% or less, about 0.006 wt.% or less, about 0.005 wt.% or less, or any range or value therebetween. In some embodiments, the anionic surfactant (e.g., phosphate surfactant) is present in the composition at a concentration of less than 0.5 wt.%, based on the total weight of the polishing composition.
[0069] In some embodiments, the anionic surfactant (e.g., phosphate surfactant) is present in an amount of about 0.001 wt % to about 1.0 wt %, about 0.002 wt % to about 1.0 wt %, about 0.003 wt % to about 1.0 wt %, about 0.004 wt % to about 1.0 wt %, about 0.005 wt % to about 1.0 wt %, about 0.006 wt % to about 1.0 wt %, about 0.007 wt % to about 1.0 wt %, about 0.008 wt % to about 1.0 wt %, about 0.009 wt % to about 1.0 wt %, about 0.01 wt % to about 1.0 wt %, or about 0.02 wt % to about 1.0 wt %, based on the total weight of the polishing composition. .0% by weight, about 0.03% to about 1.0% by weight, about 0.04% to about 1.0% by weight, about 0.05% to about 1.0% by weight, about 0.06% to about 1.0% by weight, about 0.07% to about 1.0% by weight, about 0.08% to about 1.0% by weight, about 0.09% to about 1.0% by weight , about 0.1% to about 1.0% by weight, 0.001% to about 0.5% by weight, about 0.002% to about 0.5% by weight, about 0.003% to about 0.5% by weight, about 0.004% to about 0.5% by weight, about 0.005% to about 0.5% by weight, about 0.006% to about 0.5% by weight, about 0.007 weight% to about 0.5 weight%, about 0.008 weight% to about 0.5 weight%, about 0.009 weight% to about 0.5 weight%, about 0.01 weight% to about 0.5 weight%, about 0.02 weight% to about 0.5 weight%, about 0.03 weight% to about 0.5 weight%, about 0.04 weight% to about 0.5 weight%, about 0. 05% by weight to about 0.5% by weight, about 0.06% to about 0.5% by weight, about 0.07% to about 0.5% by weight, about 0.08% to about 0.5% by weight, about 0.09% to about 0.5% by weight, about 0.1% to about 0.5% by weight, 0.001% to about 0.3% by weight, about 0.002% by weight ~0.3% by weight, approximately 0.003% by weight ~ approximately 0.3% by weight, approximately 0.004% by weight ~ approximately 0.3% by weight, approximately 0.005% by weight ~ approximately 0.3% by weight, approximately 0.006% by weight ~ approximately 0.3% by weight, approximately 0.007% by weight ~ approximately 0.3% by weight, approximately 0.008% by weight ~ approximately 0.3% by weight, approximately 0.009% by weight Amount %~about 0.3 weight%, about 0.01 weight%~about 0.3 weight%, about 0.02 weight%~about 0.3 weight%, about 0.03 weight%~about 0.3 weight%, about 0.04 weight%~about 0.3 weight%, about 0.05 weight%~about 0.3 weight%, about 0.06 weight%~about 0.3 weight%, about 0.07 weight%~about 0.3% by weight, about 0.08% to about 0.3% by weight, about 0.09% to about 0.3% by weight, about 0.1% to about 0.3% by weight, or any range or value therebetween.
[0070] Additional Surfactants In some embodiments, the polishing composition according to the present disclosure has the following formula (II):
[0071] [ka]
[0072] (wherein m is propylene oxide (PO) weight % and is 20% to 60% by weight of the total PO and EO units, n is ethylene oxide (EO) weight % and is 40% to 80% by weight of the total PO and EO units, and R is C 2-7 The weight ratio of EO to PO (EO:PO) is 2:3 to 4:1. The composition may include one or more surfactants according to the present invention.
[0073] In some embodiments, m is about 20% by weight, 25% by weight, 30% by weight, 35% by weight, 40% by weight, 45% by weight, 50% by weight, 55% by weight, or 60% by weight (or ranges therebetween) of the total PO and EO units in the surfactant of formula (II). In some embodiments, the number of EO units in the surfactant is about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, or 50. In some embodiments, n is about 40% by weight, 45% by weight, 50% by weight, 55% by weight, 60% by weight, 65% by weight, 70% by weight, 75% by weight, or 80% by weight (or ranges therebetween) of the total PO and EO units in the surfactant of formula (II). In some embodiments, the number of PO units in the surfactant is about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, or 50. In some embodiments, the weight ratio of EO to PO (EO:PO) is 2:3, 1:1, 4:3, 5:3, 2:1, 7:3, 8:3, 3:1, 10:3, 11:3, or 4:1, or a range therebetween. In some embodiments, R is a C2, C3, C4, C5, C6, or C7 alkyl, which may be branched or linear and may be optionally substituted. In some embodiments, the surfactant of formula (II) comprises a polyalkylene glycol monobutyl ether (e.g., UCON-50-400, UCON-50-2000, or any of the similar compounds described in U.S. Pat. No. 11,001,733, the entirety of which is incorporated herein by reference).
[0074] In some embodiments, the surfactant of formula (II) has a molecular weight of about 1000 g / mol or more, about 1100 g / mol or more, about 1200 g / mol or more, about 1300 g / mol or more, about 1400 g / mol or more, about 1500 g / mol or more, about 1600 g / mol or more, about 1700 g / mol or more, about 1800 g / mol or more, about 1900 g / mol or more, about 2000 g / mol or more, about 2100 g / mol or more, about 2200 g / mol or more, about 2300 g / mol or more, about 2400 g / mol In some embodiments, the molecular weight is about 2500 g / mol or more, about 2600 g / mol or more, about 2700 g / mol or more, about 2800 g / mol or more, about 2900 g / mol or more, about 3000 g / mol or more, about 3500 g / mol or more, about 4000 g / mol or more, about 4500 g / mol or more, about 5000 g / mol or more, about 5500 g / mol or more, about 6000 g / mol or more, about 6500 g / mol or more, or about 7000 g / mol or more, or any range or value therebetween. In some embodiments, the surfactant of formula (II) is about 1000 g / mol, 1100 g / mol, about 1200 g / mol, about 1300 g / mol, about 1400 g / mol, about 1500 g / mol, about 1600 g / mol, about 1700 g / mol, about 1800 g / mol, about 1900 g / mol, about 2000 g / mol, about 2100 g / mol, about 2200 g / mol, about 2300 g / mol ol, about 2400 g / mol, about 2500 g / mol, about 2600 g / mol, about 2700 g / mol, about 2800 g / mol, about 2900 g / mol, about 3000 g / mol, about 3500 g / mol, about 4000 g / mol, about 4500 g / mol, about 5000 g / mol, about 5500 g / mol, about 6000 g / mol, about 6500 g / mol, or about 7000 g / mol.
[0075] In some embodiments, the surfactant of formula (II) is present in the composition at a concentration by weight of about 0.01 wt % to about 1 wt %, about 0.05 wt % to about 1 wt %, about 0.1 wt % to about 1 wt %, about 0.05 wt % to about 0.1 wt %, or 0.05 wt % to about 0.5 wt %, based on the total weight of the polishing composition. In some embodiments, the surfactant of formula (II) is present in a concentration by weight of about 0.01 wt. % or more, about 0.02 wt. % or more, about 0.03 wt. % or more, about 0.04 wt. % or more, about 0.05 wt. % or more, about 0.06 wt. % or more, about 0.07 wt. % or more, about 0.08 wt. % or more, about 0.09 wt. % or more, about 0.1 wt. % or more, about 0.2 wt. % or more, about 0.3 wt. % or more, about 0.4 wt. % or more, about 0.5 wt. % or more, about 0.6 wt. % or more, about 0.7 wt. % or more, about 0.8 wt. % or more, about 0.9 wt. % or more, about 1.0 wt. % or more, or any range or value therebetween, based on the total weight of the polishing composition.
[0076] Corrosion Inhibitors The corrosion inhibitor may also be simply referred to as an inhibitor.
[0077] In some embodiments, the polishing composition according to the present disclosure includes a corrosion inhibitor (e.g., a Cu corrosion inhibitor). Without being bound to a particular theory, it is believed that the corrosion inhibitor passivates the metal surface (e.g., a Cu surface) to prevent pitting and other types of corrosion defects during CMP. As a non-limiting example, in some embodiments, the inhibitor may include one or more of the following: benzotriazole (BTA), 1,2,4-triazole, tetrazole, tolyltriazole, 4-carboxybenzotriazole, 5-carboxybenzotriazole, mercaptobenzoxazole, 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, and derivatives thereof. In some embodiments, the inhibitor includes benzotriazole (BTA).
[0078] The concentration of the corrosion inhibitor may be any suitable concentration for preventing corrosion, pitting, or etching of metals, such as Cu, at the pH of the polishing composition. In some embodiments, the inhibitor is present in an amount of about 0.001 wt% or more, about 0.002 wt% or more, about 0.003 wt% or more, about 0.004 wt% or more, about 0.005 wt% or more, about 0.006 wt% or more, about 0.007 wt% or more, about 0.008 wt% or more, about 0.009 wt% or more, about 0.01 wt% or more, about 0.02 wt% or more, about 0.03 wt% or more, about 0.04 wt% or more, about 0.05 wt% or more, about 0.06 wt% or more, about 0.07 wt% or more, about 0.008 wt% or more, about 0.009 wt% or more, about 0.01 wt% or more, about 0.02 wt% or more, about 0.03 wt% or more, about 0.04 wt% or more, about 0.05 wt% or more, about 0.05 wt% or more, about 0.06 wt% or more, about 0.07 wt% or more, about 0.08 wt% or more, about 0.009 wt% or more, about 0.01 wt% or more, about 0.02 wt% or more, about 0.03 wt% or more, about 0.04 wt% or more, about 0.05 wt% or more, about 0.06 wt% or more, about 0.06 wt% or more, about 0.06 wt% or more, about 0.06 wt% or more, about 0.0 It is present in the polishing composition at a concentration of .04 wt.% or more, about 0.05 wt.% or more, about 0.06 wt.% or more, about 0.07 wt.% or more, about 0.08 wt.% or more, about 0.09 wt.% or more, about 0.1 wt.% or more, about 0.2 wt.% or more, about 0.3 wt.% or more, about 0.4 wt.% or more, about 0.5 wt.% or more, about 0.6 wt.% or more, about 0.7 wt.% or more, about 0.8 wt.% or more, about 0.9 wt.% or more, or about 1 wt.% or more.
[0079] In some embodiments, the inhibitor is present in the polishing composition at a concentration of about 1 wt.% or less, about 0.9 wt.% or less, about 0.8 wt.% or less, about 0.7 wt.% or less, about 0.6 wt.% or less, about 0.5 wt.% or less, about 0.4 wt.% or less, about 0.3 wt.% or less, about 0.2 wt.% or less, about 0.1 wt.% or less, about 0.09 wt.% or less, about 0.08 wt.% or less, about 0.07 wt.% or less, about 0.06 wt.% or less, about 0.05 wt.% or less, about 0.04 wt.% or less, about 0.03 wt.% or less, about 0.02 wt.% or less, about 0.01 wt.% or less, or any range or value therebetween, based on the total weight of the polishing composition.
[0080] In some embodiments, the inhibitor is, based on the total weight of the polishing composition, about 0.001 wt % to about 1 wt %, about 0.002 wt % to about 1 wt %, about 0.003 wt % to about 1 wt %, about 0.004 wt % to about 1 wt %, about 0.005 wt % to about 1 wt %, about 0.006 wt % to about 1 wt %, about 0.007 wt % to about 1 wt %, about 0.008 wt % to about 1 wt %, about 0.009 wt % to about 1 wt %, about 0.01 wt % to about 1 wt %, about 0.02 wt % to about 1 wt %, about 0.03 wt % to about 1 wt %, about 0.04 wt % to about 1 wt %, or about 0.05 wt % to about 1 wt %, based on the total weight of the polishing composition. 1% by weight, about 0.06% to about 1% by weight, about 0.07% to about 1% by weight, about 0.08% to about 1% by weight, about 0.09% to about 1% by weight, about 0.1% to about 1% by weight, about 0.2% to about 1% by weight, about 0.3% to about 1% by weight, about 0.4% to about 1% by weight, about 0. 5% to about 1% by weight, 0.001% to about 0.5% by weight, about 0.002% to about 0.5% by weight, about 0.003% to about 0.5% by weight, about 0.004% to about 0.5% by weight, about 0.005% to about 0.5% by weight, about 0.006% to about 0.5% by weight, about 0.007% by weight Amount %~about 0.5 weight%, about 0.008 weight%~about 0.5 weight%, about 0.009 weight%~about 0.5 weight%, about 0.01 weight%~about 0.5 weight%, about 0.02 weight%~about 0.5 weight%, about 0.03 weight%~about 0.5 weight%, about 0.04 weight%~about 0.5 weight%, about 0.05 weight%~ About 0.5 weight%, about 0.06 weight% to about 0.5 weight%, about 0.07 weight% to about 0.5 weight%, about 0.08 weight% to about 0.5 weight%, about 0.09 weight% to about 0.5 weight%, about 0.1 weight% to about 0.5 weight%, about 0.2 weight% to about 0.5 weight%, about 0.3 weight% to about 0.5 weight%, about 0.001 weight% to about 0.2 weight%, about 0.002 weight% to about 0.2 weight%, about 0.003 weight% to about 0.2 weight%, about 0.004 weight% to about 0.2 weight%, about 0.005 weight% to about 0.2 weight%, about 0.006 weight% to about 0.2 weight%, about 0.007 weight% to about 0.2 weight% , about 0.008% to about 0.2% by weight, about 0.009% to about 0.2% by weight, about 0.01% to about 0.2% by weight, about 0.02% to about 0.2% by weight, about 0.03% to about 0.2% by weight, about 0.04% to about 0.2% by weight, about 0.05% to about 0.2% by weight, about 0.06wt%~about 0.2wt%, about 0.07wt%~about 0.2wt%, about 0.08wt%~about 0.2wt%, about 0.09wt%~about 0.2wt%, about 0.1wt%~about 0.2wt%, about 0.001wt%~ Approximately 0.1% by weight, approximately 0.002% by weight to approximately 0.1% by weight, approximately 0.003% by weight to approximately 0.1% by weight, approximately 0.004% by weight to approximately 0.1% by weight, approximately 0.005% by weight to approximately 0.1% by weight, approximately 0.006% by weight to approximately It is present in the polishing composition at a concentration of 0.1% by weight, about 0.007% by weight to about 0.1% by weight, about 0.008% by weight to about 0.1% by weight, about 0.009% by weight to about 0.1% by weight, about 0.01% by weight to about 0.1% by weight, about 0.02% by weight to about 0.1% by weight, about 0.03% by weight to about 0.1% by weight, about 0.04% by weight to about 0.1% by weight, about 0.05% by weight to about 0.1% by weight, or any range or value therebetween.
[0081] Water-soluble polymer In some embodiments, the polishing composition according to the present disclosure includes one or more water-soluble polymers. In some embodiments, the water-soluble polymer is in a solid form (powder form) at 25° C. and can be dissolved in water, thereby becoming liquid. The water-soluble polymer-containing liquid can be prepared by dissolving the water-soluble polymer in water. Here, "water-soluble" means that the solubility in water (25° C.) is 1 g / 100 mL or more, and "polymer" refers to a (co)polymer having a repeating unit in its molecular structure and a weight-average molecular weight (Mw) of 1,000 or more. In this specification, the "weight-average molecular weight" can be a value of the weight-average molecular weight (polyethylene glycol equivalent) measured by gel permeation chromatography (GPC). The weight-average molecular weight can be measured by the following apparatus and conditions: GPC equipment: Shimadzu Corporation Model: Prominence + ELSD detector (ELSD-LTII) Column: VP-ODS (Shimadzu Corporation) Mobile phase A:MeOH B: 1% acetic acid solution Flow rate: 1mL / min Detector: ELSD temp. 40℃, Gain 8, N2GAS 350kPa Oven temperature: 40℃ Injection volume: 40μL.
[0082] In some embodiments, the weight average molecular weight of the water-soluble polymer (e.g., pullulan) is, for example, but not limited to, 1,000 to 1,000,000, 10,000 to 700,000, 100,000 to 600,000, or 200,000 to 500,000. In some examples, the kinetic viscosity of an aqueous solution of the water-soluble polymer (converted to a concentration of 10% (w / w)) obtained by dissolving the water-soluble polymer (e.g., pullulan) in deionized water is, for example, 100 to 180 mm as measured by an Ubbelohde viscometer (measurement temperature 30°C). 2 / second.
[0083] The one or more water-soluble polymers are not particularly limited. Non-limiting examples of water-soluble polymers include one or more polysaccharides (e.g., alginic acid, pectic acid, agar, curdlan, and pullulan); cellulose derivatives (e.g., hydroxymethylcellulose, hydroxyethylcellulose (HEC), hydroxypropylcellulose, hydroxyethylmethylcellulose, hydroxypropylmethylcellulose, methylcellulose, ethylcellulose, ethylhydroxyethylcellulose, or carboxymethylcellulose; imine derivatives such as poly(N-acylalkyleneimines); polyvinyl alcohol (PVA); modified (cationically or non-ionically modified) polyvinyl alcohol; poly(N-vinylacetamide) (PNVA); polyvinylpyrrolidone (PVP); polyvinylcaprolactam; polyoxyalkylenes (e.g., polyoxyethylene); polypropylene glycol (PPG), polyethylene glycol (PEG), PEG-PPG copolymers or block copolymers (e.g., PEG-PPG, PEG-PPG-PEG, PPG-PEG-PPG, etc.), and copolymers or mixtures thereof. In some embodiments, the water-soluble polymer comprises pullulan. One or more water-soluble polymers may be used alone or as a mixture of two or more types.
[0084] In some embodiments, the water-soluble polymer contained in the polishing composition according to the present disclosure includes a polysaccharide. In some embodiments, the water-soluble polymer contained in the polishing composition according to the present disclosure includes a polysaccharide consisting of glucose. In some embodiments, the water-soluble polymer contained in the polishing composition according to the present disclosure includes pullulan. In some embodiments, 80% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, or 99% by weight or more of the water-soluble polymer contained in the polishing composition according to the present disclosure is composed of polysaccharide. Here, polysaccharide is a general term for a substance in which a large number of monosaccharide molecules are polymerized by glycosidic bonds. The concept of polysaccharide includes a sugar in which multiple (two or more) monosaccharides are bound to a monosaccharide.
[0085] In some embodiments, the water-soluble polymer contained in the polishing composition according to the present disclosure is composed of 80% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, or 99% by weight or more of a polysaccharide consisting only of glucose (e.g., pullulan).
[0086] In some embodiments, the water soluble polymer is about 500 g / mol or more, about 1000 g / mol or more, about 1500 g / mol or more, about 2000 g / mol or more, about 2500 g / mol or more, about 3000 g / mol or more, about 3500 g / mol or more, about 4000 g / mol or more, about 4500 g / mol or more, about 5000 g / mol or more, about 5500 g / mol or more, about 6000 g / mol or more. , about 6500g / mol or more, about 7000g / mol or more, about 7500g / mol or more, about 8000g / mol or more, about 8500g / mol or more, about 9000g / mol or more, about 9500g / mol l or more, about 10,000 g / mol or more, about 15,000 g / mol or more, about 20,000 g / mol or more, about 25,000 g / mol or more, about 30,000 g / mol or more, about 35,000 g / mol or more, about 40000g / mol or more, about 45000g / mol or more, about 50000g / mol or more, about 55000g / mol or more, about 60000g / mol or more, about 65000g / mol or more, about 7000 0g / mol or more, about 75000g / mol or more, about 80000g / mol or more, about 85000g / mol or more, about 90000g / mol or more, about 95000g / mol or more, about 100000g / m ol or more, about 150,000 g / mol or more, about 200,000 g / mol or more, about 250,000 g / mol or more, about 300,000 g / mol or more, about 350,000 g / mol or more, about 400,000 g / mol or more, about 450,000 g / mol or more, about 500,000 g / mol or more, or any range or value therebetween (e.g., 5,000 to 300,000 g / mol).
[0087] In some embodiments, the one or more water-soluble polymers are present in an amount of about 0.001% by weight to about 5% by weight, about 0.01% by weight to about 0.5% by weight, about 0.005% by weight to about 5% by weight, about 0.01% by weight to about 5% by weight, about 0.05% by weight to about 5% by weight, about 0.1% by weight to about 5% by weight, about 0.5% by weight to about 5% by weight, about 1% by weight to about 5% by weight, about 0.001% by weight to about 5% by weight, about 0.01% by weight to about 5% by weight, about 0.05% by weight to about 5% by weight, about 0.1% by weight to about 5% by weight, about 0.5% by weight to about 5% by weight, about 0.005% by weight to about 5% by weight, about 0.01% by weight to about 5% by weight, about 0.05% by weight to about 5% by weight, about 0.1% by weight to about 5% by weight, about 0.5% by weight to about 5% by weight, about 0.0 ... .001% to about 1% by weight, about 0.005% to about 1% by weight, about 0.01% to about 1% by weight, about 0.05% to about 1% by weight, about 0.1% to about 1% by weight, about 0.5% by weight ~1% by weight, approximately 0.001% by weight ~ approximately 0.1% by weight, approximately 0.005% by weight ~ approximately 0.1% by weight, approximately 0.01% by weight ~ approximately 0.1% by weight, approximately 0.05% by weight ~ approximately 0.1% by weight, approximately 0.00 1% by weight to about 0.1% by weight, or any range or value therebetween (e.g., about 0.001% by weight, about 0.002% by weight, about 0.003% by weight, about 0.004% by weight, about 0.005% by weight, about 0.006% by weight, about 0.007% by weight, about 0.008% by weight, about 0.009% by weight, about 0.01% by weight, about 0.02% by weight, about 0.03% by weight, about 0.04% by weight, It is present in a concentration by weight of about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.1%, about 0.2%, about 0.3%, about 0.4%, about 0.5%, about 0.6%, about 0.7%, about 0.8%, about 0.9%, about 1%, about 2%, about 3%, about 4%, or about 5%.
[0088] In some embodiments, the water-soluble polymer is present in the polishing composition at a concentration of more than 0.01 wt %, based on the total weight of the polishing composition. In some embodiments, the water-soluble polymer is present at a concentration by weight of 5 wt % or less, 4 wt % or less, 3 wt % or less, 2 wt % or less, 1 wt % or less, 0.9 wt % or less, 0.7 wt % or less, 0.5 wt % or less, 0.3 wt % or less, 0.1 wt % or less, or any range or value therebetween, based on the total weight of the polishing composition.
[0089] Electronic conductivity controller In some embodiments, the polishing composition according to the present disclosure further comprises a salt that functions as an electrical conductivity (EC) control agent. The EC control agent may be any salt suitable for the polishing composition (e.g., suitable for adjusting the ionic strength of the composition). For example, in some embodiments, the EC control agent is a citrate, such as potassium citrate (e.g., tripotassium citrate). In some embodiments, the EC control agent is a nitrate, such as sodium nitrate, potassium nitrate, or ammonium nitrate. In some embodiments, the EC control agent is an acetate, such as sodium acetate, potassium acetate, or ammonium acetate. In some embodiments, the EC control agent is a halogen salt (e.g., NaCl or KCl). In some embodiments, the EC control agent may include KHCO3 or NaHCO3. The EC control agent may also be in a hydrate form before addition. In some embodiments, the electrical conductivity control agent included in the polishing composition according to the present disclosure comprises a citrate. In some embodiments, the salt in the citrate is at least one of sodium, potassium, and ammonium.
[0090] In some embodiments, the one or more EC control agents are, based on the total weight of the polishing composition, about 0.001 wt % to about 5 wt %, about 0.005 wt % to about 5 wt %, about 0.01 wt % to about 5 wt %, about 0.05 wt % to about 5 wt %, about 0.1 wt % to about 5 wt %, about 0.5 wt % to about 5 wt %, about 1 wt % to about 5 wt %, or about 0.001 wt % to about 1 wt %, based on the total weight of the polishing composition. , about 0.005% to about 1% by weight, about 0.01% to about 1% by weight, about 0.05% to about 1% by weight, about 0.1% to about 1% by weight, about 0.5% to about 1% by weight, about 0.0 01% by weight ~ approximately 0.1% by weight, approximately 0.005% by weight ~ approximately 0.1% by weight, approximately 0.01% by weight ~ approximately 0.1% by weight, approximately 0.05% by weight ~ approximately 0.1% by weight, approximately 0.001% by weight ~ approximately 0.1 % by weight, or any range or value therebetween (e.g., about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0. ... %, about 0.06%, about 0.07%, about 0.08%, about 0.09%, about 0.1%, about 0.2%, about 0.3%, about 0.4%, about 0.5%, about 0.6%, about 0.7%, about 0.8%, about 0.9%, about 1%, about 2%, about 3%, about 4%, or about 5% by weight.
[0091] In some embodiments, the one or more EC control agents are present in the polishing composition at a concentration of less than 1 wt%, based on the total weight of the polishing composition. In some embodiments, the one or more EC control agents are present in the polishing composition at a concentration of less than 0.5 wt%, based on the total weight of the polishing composition. In some embodiments, the one or more EC control agents are present in the polishing composition at a concentration of more than 0.03 wt%, based on the total weight of the polishing composition. In some embodiments, the one or more EC control agents are present in the polishing composition at a concentration by weight of 0.001 wt% or more, 0.003 wt% or more, 0.005 wt% or more, 0.007 wt% or more, 0.009 wt% or more, 0.01 wt% or more, 0.03 wt% or more, 0.05 wt% or more, 0.07 wt% or more, 0.09 wt% or more, or any range or value therebetween, based on the total weight of the polishing composition. In some embodiments, the one or more EC control agents are present in the polishing composition at a concentration by weight of 0.9 wt.% or less, 0.8 wt.% or less, 0.7 wt.% or less, 0.6 wt.% or less, 0.5 wt.% or less, 0.4 wt.% or less, 0.3 wt.% or less, 0.2 wt.% or less, or any range or value therebetween, based on the total weight of the polishing composition.
[0092] In some embodiments, the EC regulator is a citrate salt, such as tripotassium citrate or diammonium citrate.
[0093] Oxidizing agent In some embodiments, the polishing composition of the present disclosure may include at least one oxidizing agent. The oxidizing agent may be added to the polishing composition to oxidize the metal surface (e.g., Cu) of the polishing object, thereby improving the metal removal rate of the polishing process. In some embodiments, the oxidizing agent is added to the polishing composition only immediately before use (e.g., "point of use" or "POU"). In other embodiments, the oxidizing agent is mixed with other components of the polishing composition at about the same time during the manufacturing procedure. In some embodiments, the composition is manufactured and sold as a stock composition, and the end customer can choose to dilute the stock composition as needed and / or add a suitable amount of oxidizing agent before use.
[0094] In some embodiments, non-limiting examples of oxidizing agents that may be used include peroxides (e.g., hydrogen peroxide, sodium peroxide, barium peroxide, etc.), organic oxidizing agents, ozone water, silver (II) salts, iron (III) salts, permanganic acid, chromic acid, dichromate, peroxodisulfuric acid, peroxolinic acid, peroxosulfuric acid, peroxoboric acid, performic acid, peracetic acid, perbenzoic acid, perphthalic acid, hypochlorous acid, hypobromous acid, hypoiodous acid, chloric acid, chlorous acid, perchloric acid, bromic acid, iodic acid, periodic acid, persulfuric acid, dichloroisocyanuric acid, and salts thereof, but are not limited thereto. The oxidizing agents may be used alone or as a mixture of two or more types. In some embodiments, the oxidizing agent includes hydrogen peroxide, ammonium persulfate, periodic acid, hypochlorous acid, sodium dichloroisocyanurate, or mixtures thereof. In some embodiments, the oxidizing agent comprises hydrogen peroxide (e.g., 30% H2O2). In some embodiments, the polishing composition of the present disclosure comprises at least 80 wt.%, at least 85 wt.%, at least 90 wt.%, at least 95 wt.%, or at least 99 wt.% of the oxidizing agent contained in the polishing composition of the present disclosure is hydrogen peroxide.
[0095] In some embodiments, the one or more oxidizing agents may be present in an amount of about 0.1 wt % or more, about 0.15 wt % or more, about 0.2 wt % or more, about 0.25 wt % or more, about 0.3 wt % or more, about 0.35 wt % or more, about 0.4 wt % or more, about 0.45 wt % or more, about 0.5 wt % or more, about 0.55 wt % or more, about 0.60 wt % or more, about 0.65 wt % or more, about 0.7 wt % or more, about 0.75 wt % or more, about 0.8 wt % or more, about 0.85 wt % or more, about 0.9 wt % or more, about 0.95 wt % or more, about 1.0 wt % or more, about 1.1 wt % or more, about 1.2 wt % or more, about 1.3 wt % or more, about
[0033] The composition is present in a concentration by weight of 1.4% by weight or more, about 1.5% by weight or more, about 1.6% by weight or more, about 1.7% by weight or more, about 1.8% by weight or more, about 1.9% by weight or more, about 2.0% by weight or more, about 2.5% by weight or more, about 3.0% by weight or more, about 3.5% by weight or more, about 4.0% by weight or more, about 4.5% by weight or more, about 5.0% by weight or more, about 5.5% by weight or more, about 6.0% by weight or more, about 6.5% by weight or more, about 7.0% by weight or more, about 7.5% by weight or more, about 8.0% by weight or more, about 8.5% by weight or more, about 9.0% by weight or more, about 9.5% by weight or more, about 10.0% by weight or more, or any range or value therebetween. In some embodiments, the one or more oxidizing agents are present in the composition in a concentration by weight of 10% by weight or less, 9% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, or any range or value therebetween, based on the total weight of the composition.
[0096] The content of one or more oxidizing agents can be reduced, and the cost related to the material of the polishing composition can be saved, and the burden related to the waste disposal after the use of the polishing composition can be reduced.By reducing the content of oxidizing agents, it is also possible to reduce the possibility of excessive oxidation of the surface.
[0097] acidic compound In some embodiments, the polishing composition according to the present disclosure comprises one or more acidic compounds. In some embodiments, the one or more acidic compounds comprise one or more organic acids (e.g., carboxylic acids, such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, and lactic acid; organic sulfuric acids, such as methanesulfonic acid, ethanesulfonic acid, and isethionic acid, and any combination thereof; and organic phosphonoacetic acids, such as 2-hydroxyphosphonoacetic acid (HPAA); and combinations thereof). In some embodiments, the organic acid is citric acid.
[0098] In some embodiments, the one or more organic acids are, based on the total weight of the polishing composition, about 0.001 wt % to about 5 wt %, about 0.01 wt % to about 0.5 wt %, about 0.005 wt % to about 5 wt %, about 0.01 wt % to about 5 wt %, about 0.05 wt % to about 5 wt %, about 0.1 wt % to about 5 wt %, about 0.5 wt % to about 5 wt %, about 1 wt % to about 5 wt %, about 0.001 Weight% to about 1% by weight, about 0.005% to about 1% by weight, about 0.01% to about 1% by weight, about 0.05% to about 1% by weight, about 0.1% to about 1% by weight, about 0.5% to about 1% by weight %, about 0.001 weight% to about 0.1 weight%, about 0.005 weight% to about 0.1 weight%, about 0.01 weight% to about 0.1 weight%, about 0.05 weight% to about 0.1 weight%, about 0.001 weight% to about 0.1% by weight, or any range or value therebetween (e.g., about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0. ... %, about 0.06 wt.%, about 0.07 wt.%, about 0.08 wt.%, about 0.09 wt.%, about 0.1 wt.%, about 0.2 wt.%, about 0.3 wt.%, about 0.4 wt.%, about 0.5 wt.%, about 0.6 wt.%, about 0.7 wt.%, about 0.8 wt.%, about 0.9 wt.%, about 1 wt.%, about 2 wt.%, about 3 wt.%, about 4 wt.%, or about 5 wt.%.
[0099] pH adjuster In some embodiments, the compositions according to the present disclosure may further comprise one or more pH adjusting agents to adjust the pH to a selected pH value. In some embodiments, the "surfactants", "phosphate surfactants", "water-soluble polymers", and "corrosion inhibitors" disclosed above are not considered to be pH adjusting agents.
[0100] The pH adjusting agent is not particularly limited, and any suitable pH adjusting agent may be used to bring the pH of the composition to any desired range as described above.In some embodiments, one or more pH adjusting agents may comprise, consist essentially of, or consist of inorganic compounds, organic compounds, or combinations thereof.In some embodiments, one or more pH adjusting agents may comprise inorganic acids (e.g., hydrochloric acid, hydrobromic acid, hydroiodic acid, sulfuric acid, nitric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid); organic acids (e.g., carboxylic acids, such as citric acid, formic acid, acetic acid, propionic acid, benzoic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, maleic acid, phthalic acid, malic acid, tartaric acid, and lactic acid); and / or organic acids (e.g., methanesulfonic acid, ethanesulfonic acid, isethionate, etc.). In some embodiments, the one or more pH adjusters may include di- or higher-value acids of the above acids (e.g., sulfuric acid, carbonic acid, phosphoric acid, oxalic acid, etc.), which may have one or more protons (H + ) may be in the form of a base (e.g., ammonium bicarbonate or ammonium hydrogen phosphate), although any counterion may be used (e.g., a weakly basic cation such as ammonium, triethanolamine, etc.). In some embodiments, the one or more pH adjusters include nitric acid.
[0101] In some embodiments, the one or more pH adjusters may include one or more hydroxides of alkali metals (e.g., NaOH, KOH) or salts thereof (e.g., carbonates, bicarbonates, sulfates, acetates, etc.); quaternary ammonium compounds (e.g., tetramethylammonium, tetraethylammonium, tetrabutylammonium, etc.); quaternary ammonium hydroxides (e.g., tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide) or salts thereof; ammonia; amines, or any other suitable pH adjusters.
[0102] In some embodiments, the one or more pH adjusters are, based on the total weight of the polishing composition, about 0.001 wt % to about 5 wt %, about 0.01 wt % to about 0.5 wt %, about 0.005 wt % to about 5 wt %, about 0.01 wt % to about 5 wt %, about 0.05 wt % to about 5 wt %, about 0.1 wt % to about 5 wt %, about 0.5 wt % to about 5 wt %, about 1 wt % to about 5 wt %, about 0.00 1% to about 1% by weight, about 0.005% to about 1% by weight, about 0.01% to about 1% by weight, about 0.05% to about 1% by weight, about 0.1% to about 1% by weight, about 0.5% to about 1% by weight Amount%, about 0.001 weight% to about 0.1 weight%, about 0.005 weight% to about 0.1 weight%, about 0.01 weight% to about 0.1 weight%, about 0.05 weight% to about 0.1 weight%, about 0.001 weight% to about 0.1% by weight, or any range or value therebetween (e.g., about 0.001%, about 0.002%, about 0.003%, about 0.004%, about 0.005%, about 0.006%, about 0.007%, about 0.008%, about 0.009%, about 0.01%, about 0.02%, about 0.03%, about 0.04%, about 0.05%, about 0.06%, about 0.07%, about 0.08%, about 0. ... %, about 0.06 wt.%, about 0.07 wt.%, about 0.08 wt.%, about 0.09 wt.%, about 0.1 wt.%, about 0.2 wt.%, about 0.3 wt.%, about 0.4 wt.%, about 0.5 wt.%, about 0.6 wt.%, about 0.7 wt.%, about 0.8 wt.%, about 0.9 wt.%, about 1 wt.%, about 2 wt.%, about 3 wt.%, about 4 wt.%, or about 5 wt.%.
[0103] pH of the polishing composition The pH adjuster may be present in any amount suitable to achieve the desired pH value as discussed above. In some embodiments, the pH of the composition is basic (e.g., greater than 7). In some embodiments, the pH of the composition is 7 or more, greater than 7, 7.1 or more, 7.2 or more, 7.3 or more, 7.4 or more, 7.5 or more, 7.6 or more, 7.7 or more, 7.8 or more, 7.9 or more, 8.0 or more, 8.1 or more, 8.2 or more, 8.3 or more, 8.4 or more, 8.5 or more, 8.6 or more, 8.7 or more, 8.8 or more, 8.9 or more, 9.0 or more, 9.1 or more, 9.2 or more, 9.3 or more, 9.4 or more, 9.5 or more, 9.6 or more, 9.7 or more, 9.8 or more, 9.9 or more, 10.0 or more, or any range or value therebetween. In some embodiments, the pH of the composition is greater than 8.
[0104] In some embodiments, the pH of the composition is about 11.0 or less, about 10.5 or less, about 10.0 or less, about 9.9 or less, about 9.8 or less, about 9.7 or less, about 9.6 or less, about 9.5 or less, about 9.4 or less, about 9.3 or less, about 9.2 or less, about 9.1 or less, about 9.0 or less, about 8.9 or less, about 8.8 or less, about 8.7 or less, about 8.6 or less, about 8.5 or less, about 8.4 or less, about 8.3 or less, about 8.2 or less, about 8.1 or less, about 8.0 or less, about 7.9 or less, about 7.8 or less, about 7.7 or less, about 7.6 or less, about 7.5 or less, or any range or value therebetween. In some embodiments, the pH of the composition is less than 11. In some embodiments, the pH of the composition is greater than 8 and less than 10.5.
[0105] In some embodiments, the pH of the composition is 7-11, 7-10.5, 7-10, 7-9.5, 7-9, 7-8.5, 7-8, 7.5-10, 7.5-9.5, 7.5-9, 7.5-8.5, 7.5-8, 8-11, 8-10.5, 8-10, 8-9.5, 8-9, 8-8.5, 8.5-11, 8.5-10.5, 8.5-10, 8.5-9.5, 8.5-9, 9-11, 9-10.5, 9-10, 9-9.5, 9.5-11, 9.5-10.5, 9.5-10, 10-11, or any range or value therebetween. In some embodiments, the pH of the composition is about 7, about 7.5, about 8, about 8.5, about 9, about 9.5, about 10, about 10.5, about 11, or any range or value therebetween. In some embodiments, the pH of the composition is greater than 8 and less than 11.
[0106] Other Additives In some embodiments, the composition may include other additives in any concentration. However, it is desirable not to add unnecessary components that may cause the presence of surface defects. Thus, any other additives, if present at all, are desirably present in relatively low concentrations (e.g., 0.1% by weight or less, 0.05% by weight or less, 0.01% by weight or less, 0.005% by weight or less, 0.001% by weight or less, 0.0005% by weight or less, 0.0001% by weight or less, 0.0001% by weight to 0.1% by weight, 0.0001% by weight to 0.01% by weight, or 0.0001% by weight to 0.001% by weight, etc.). Examples of other additives include preservatives, biocides (e.g., isothiazolinones, such as methylisothiazolinone ("MIT"), benzoisothiazolinone ("BIT"), etc.), oil-soluble gases, etc.
[0107] Liquid Carrier The polishing composition according to the present disclosure includes a liquid carrier. The liquid carrier of the polishing composition is not particularly limited. In some embodiments, the liquid carrier is water, for example, deionized water. The liquid carrier may also be an aqueous solution containing, for example, a suitable pH adjuster. In some embodiments, the liquid carrier may include one or more organic solvents, for example, an alcohol compound, for example, an aliphatic alcohol having 2 to 6 carbon atoms and a glycol ether having 3 to 10 carbon atoms. Examples of aliphatic alcohols having 2 to 6 carbon atoms include ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, tert-butanol, pentanol, hexanol, ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, glycerin, 1,2,4-butanetriol, 1,2,6-hexanetriol, erythritol, D-threitol, L-threitol, D-arabinitol, L-arabinitol, ribitol, xylitol, mannitol, and sorbitol. Examples of glycol ethers having 3 to 10 carbon atoms include methyl glycol, methyl diglycol, methyl triglycol, isopropyl glycol, isopropyl diglycol, butyl glycol, butyl diglycol, butyl triglycol, isobutyl glycol, isobutyl diglycol, hexyl glycol, hexyl diglycol, 2-ethylhexyl glycol, 2-ethylhexyl diglycol, aryl glycol, phenyl glycol, phenyl diglycol, benzyl glycol, methyl propylene glycol, methyl propylene diglycol, methyl propylene triglycol, propyl propylene glycol, propyl propylene diglycol, butyl propylene glycol, butyl propylene diglycol, and phenyl propylene glycol. In some embodiments, 80% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, or 99% by weight or more of the liquid carrier contained in the polishing composition is composed of water.
[0108] Polishing method In another aspect, the present disclosure relates to a method for polishing a substrate surface, the substrate surface comprising a metal interconnect and a barrier layer on a SiO2 layer derived from tetraethyl orthosilicate ("TEOS"). The present disclosure relates to a method for polishing a substrate surface, the substrate surface comprising copper and TEOS, the method comprising: contacting the substrate surface with a polishing composition of any of the embodiments disclosed herein; and moving a polishing pad relative to the substrate surface while contacting the polishing composition with the substrate surface; wherein the polishing achieves a topographical correction of 30 nm or more in terms of dishing of Cu relative to the TEOS surface. (For purposes of this disclosure, a "TEOS substrate" or a "TEOS layer" refers to a SiO2 layer derived from tetraethyl orthosilicate. Similarly, a "TEOS surface" refers to the top surface of the TEOS layer.) Cu removal rate (RR Cu ) In some embodiments, the polishing step achieves a copper removal rate of 250 Å / min or less, 240 Å / min or less, 230 Å / min or less, 220 Å / min or less, 210 Å / min or less, 200 Å / min or less, 190 Å / min or less, 180 Å / min or less, 170 Å / min or less, 160 Å / min or less, 150 Å / min or less, or any range or value therebetween. In some embodiments, the polishing step achieves a copper removal rate of 150 Å / min or more, 160 Å / min or more, 170 Å / min or more, 180 Å / min or more, 190 Å / min or more, 200 Å / min or more, 210 Å / min or more, 220 Å / min or more, 230 Å / min or more, 240 Å / min or more, 250 Å / min or more, or any range or value therebetween. In some embodiments, the polishing step achieves a TEOS removal rate of 200 Å / min or less, 190 Å / min or less, 180 Å / min or less, 170 Å / min or less, 160 Å / min or less, 150 Å / min or less, 140 Å / min or less, 130 Å / min or less, 120 Å / min or less, or any range or value therebetween.
[0109] TEOS removal rate (RR TEOS ) In some embodiments, the polishing step achieves a TEOS removal rate of 100 Å / min or more, 110 Å / min or more, 120 Å / min or more, 130 Å / min or more, 140 Å / min or more, 150 Å / min or more, 160 Å / min or more, 170 Å / min or more, 180 Å / min or more, 190 Å / min or more, 200 Å / min or more, or any range or value therebetween. In some embodiments, the polishing step achieves a TEOS removal rate of 200 Å / min or less, 190 Å / min or less, 180 Å / min or less, 170 Å / min or less, 160 Å / min or less, 150 Å / min or less, 140 Å / min or less, 130 Å / min or less, 120 Å / min or less, or any range or value therebetween.
[0110] Ta removal rate (RR Ta ) In some embodiments, the polishing step achieves a tantalum removal rate of 100 Å / min or more, 110 Å / min or more, 120 Å / min or more, 130 Å / min or more, 140 Å / min or more, 150 Å / min or more, 160 Å / min or more, 170 Å / min or more, 180 Å / min or more, 190 Å / min or more, 200 Å / min or more, or any range or value therebetween. In some embodiments, the polishing step achieves a tantalum removal rate of 200 Å / min or less, 190 Å / min or less, 180 Å / min or less, 170 Å / min or less, 160 Å / min or less, 150 Å / min or less, 140 Å / min or less, 130 Å / min or less, 120 Å / min or less, or any range or value therebetween.
[0111] RR Ta / RR TEOS In some embodiments, the polishing step achieves a Ta / TEOS polishing rate ratio of 1.00 or greater, 1.10 or greater, 1.15 or greater, 1.20 or greater, 1.25 or greater, 1.30 or greater, 1.35 or greater, 1.40 or greater, 1.45 or greater, or 1.50 or greater, or any range or value therebetween.
[0112] Topography Correction In practice, a height difference typically occurs after Cu polishing, and the barrier polishing composition is evaluated for topography correction (nm). Thus, referring to FIG. 1F, if the height difference between the TEOS reference surface and the top of the Cu layer after the barrier layer polishing is smaller than the height difference before the barrier layer polishing, the topography is said to be corrected, and the topography correction (before (nm)-after (nm)) represents a positive value. Similarly, if the height difference between the TEOS reference plane and the top of the Cu layer after the barrier layer is polished is greater than the height difference before the barrier layer is polished, the topography correction (before (nm) - after (nm)) represents a negative value. Thus, the more "positive" or "less negative" the topography correction (nm), the better a given polishing composition is able to correct (or avoid further deterioration of) the non-ideal topography. On the other hand, the more "positive" or "more negative" the topography correction (nm), the worse a given polishing composition is at correcting (or avoiding further deterioration of) the non-ideal topography. For purposes of this disclosure, a positive topography value (nm) represents that the top of the Cu layer is below the TEOS reference plane.
[0113] In some embodiments, the polishing step achieves a topography correction of at least about 25 nm, at least about 30 nm, at least about 32 nm, at least about 35 nm, at least about 38 nm, at least about 40 nm, or any range or value therebetween (e.g., "9 μm / 1 μm dishing"), as determined by the amount of dishing before polishing (nm) minus the amount of dishing after polishing (nm).
[0114] In the following, some specific embodiments contemplated by the present disclosure will be described in detail. Although various embodiments are described herein, it will be understood that it is not intended to limit the present technology to the described embodiments. On the contrary, it is intended to cover changes, modifications, and equivalents that may be included within the spirit and scope of the present technology as defined in the appended claims.
[0115] The present invention encompasses the following aspects and configurations.
[0116] A polishing composition comprising: an abrasive containing silica particles having an average primary particle size of greater than 1.12 nm and / or an average secondary particle size of greater than 30 nm; a phosphate surfactant; a water-soluble polymer; and an electrical conductivity control agent; wherein the silica particles have a D90 / D50 ratio of greater than 1.3 or a D90 / D10 ratio of greater than 1.7 and / or are surface-modified with an organic acid, the phosphate surfactant contains 15 or less oxyethylene units and a linear or branched C4 or higher alkylphenyl, and is present at a concentration of less than 0.5 wt.% based on the total weight of the polishing composition, the electrical conductivity control agent is present at a concentration of less than 1 wt.% based on the total weight of the polishing composition, and the pH is greater than 8 and less than 11.
[0117] 2. The polishing composition described in 1., wherein the phosphate surfactant is present at a concentration of greater than 0.01 weight percent, based on the total weight of the polishing composition.
[0118] 3. The polishing composition according to 1 or 2, wherein the water-soluble polymer comprises a polysaccharide.
[0119] 4. The polishing composition according to 3, wherein the polysaccharide is pullulan.
[0120] 5. The polishing composition according to any one of 1. to 4., wherein the electrical conductivity control agent is a citrate.
[0121] 6. The polishing composition according to 5., wherein the citrate is at least one of tripotassium citrate and diammonium citrate.
[0122] 7. The polishing composition according to any one of 1. to 6., wherein the electrical conductivity control agent is present at a concentration of more than 0.03 wt % based on the total weight of the polishing composition.
[0123] 8. The phosphate surfactant has the following formula (I): [Tail-(OC2H5)n -O] m -PO q H r (I) In the formula, OC2H5 is an oxyethylene unit, n is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15, (m, q, r) are (1, 3, 2), (2, 2, 1), or (3, 1, 0), and the tail is an alkylphenyl having a length of C4 or more.
[0124] 9. The n is 6, 7, 8 or 9, and / or the tail is C5 to C 11 9. The polishing composition according to 8., wherein the alkylphenyl is an alkylphenyl.
[0125] 10. The polishing composition described in 9., wherein the phosphate surfactant is present at a concentration of greater than 0.01 weight % based on the total weight of the polishing composition, the electrical conductivity control agent is present at a concentration of greater than 0.03 weight % based on the total weight of the polishing composition, and the silica particles have an average primary particle size of less than 78 nm and, when not surface-modified with an organic acid, have a D90 / D50 ratio of less than 1.9.
[0126] 11. The polishing composition according to claim 10, wherein the phosphate surfactant is present at a concentration of less than 0.1 weight percent, based on the total weight of the polishing composition.
[0127] 12. The polishing composition according to claim 10 or 11, wherein the electrical conductivity control agent is present at a concentration of less than 0.5 wt % based on the total weight of the polishing composition.
[0128] 13. The polishing composition according to any one of 10 to 12, wherein the water-soluble polymer is present at a concentration of more than 0.01 weight % relative to the total weight of the polishing composition. EXAMPLES
[0129] [Example 1] material and method Preparation of the Polishing Composition To investigate the effects of abrasive particle size and type, phosphate surfactant type and concentration, and conductivity control agent type and concentration on Cu, Ta, and TEOS removal rates, Ta / TEOS removal rate selectivity, and topography compensation, polishing compositions containing silica abrasive particles (see Table 1) were prepared and used to evaluate the removal rates, along with topography compensation, of TEOS and Ta and Cu films deposited on silicon wafers having a TEOS-derived thermal oxide layer.
[0130] A polishing composition containing the abrasive particles shown in Table 1 was prepared by adding deionized water, benzotriazole (BTA) as a corrosion inhibitor, a conductivity control agent (see Table 3) and an acid (organic acid) related to the conductivity control agent for pH buffering, a phosphate surfactant (see Table 2), pullulan as a water-soluble polymer, and a silica abrasive (see Table 4) with mixing, and finally adding deionized water to obtain a final volume. The pH of the composition was adjusted by adding potassium hydroxide as a pH adjuster while monitoring the pH until the selected composition pH was obtained.
[0131] pH measurement The pH of the polishing composition according to the present disclosure was determined using a Thermo-Fisher Scientific VSTAR94 pH meter.
[0132] Zeta potential measurement Zeta potential of various abrasives in the polishing composition according to the present disclosure was determined using ZETASIZER (registered trademark) (Malvern Panalytical). Zeta potential of various substrates polished using the polishing composition according to the present disclosure was determined using a SurPASS (trademark) 3 zeta potential analyzer (Anton Paar GmbH). Removal rate measurement To determine the polishing rate, the polishing composition was applied to the following substrates:
[0133] For measuring removal rate: · Ta: 2000 Å Ta on thermal oxide on Si substrate (Advantiv); · Cu: 10,000 Å epitaxial Cu on TiN on thermal oxide on silicon (Advantiv); TEOS: 10,000Å TEOS on Si substrate (Advantiv) For measuring topography correction: Patterned wafer: MIT754 mask (7000 Å Cu; 100 Å Ta; 3000 Å TEOS) The polishing rates were determined using the following polishing conditions:
[0134] · Polishing machine: 300mm polishing machine (Reflexion LK); ·Scouring pad: Fujibo H8000; ·Conditioner: 3M A82; Downforce: 1.0psi · Polishing platen rotation: 73 rpm; Head rotation: 63rpm; Slurry flow rate: 200mL / min.
[0135] The polishing rate can be calculated by measuring the thickness using an optical film thickness measuring device (ASET-f5x: manufactured by KLA-Tencor Corporation) and dividing (thickness before polishing) - (thickness after polishing) by the polishing time.
[0136] To evaluate the removal rates achieved by the polishing compositions, film thicknesses were measured before and after polishing using a Resmap resistivity mapping system (Creative Design Engineering, Inc.) for Ta and Cu films or a KLA ASET-F5X Pro optical thin film measurement system (KLA Corporation) for TEOS substrates.
[0137] Topography Corrected Measurements With reference to Figures 1A-1F, to evaluate topography correction, a patterned Si wafer with 3000 Å thermal oxide (derived from TEOS) was patterned with trenches for depositing Cu lines. As shown in Figure 1A, in a "9 / 1" pattern, the trenches are 1 μm wide with a 9 μm trench-to-trench spacing. A Ta barrier layer (100 Å) was deposited over the entire patterned wafer, followed by a 7000 Å Cu layer. With reference to Figure 1B, a Cu polishing slurry was used to polish the Cu film, leaving the barrier layer and Cu lines in the trenches.
[0138] The patterned wafer with Cu lines was then subjected to barrier layer polishing using the polishing composition according to the present disclosure according to the conditions described above. Referring to FIG. 1C, when the barrier layer polishing conditions have ideal Ta / TEOS and Cu / TEOS selectivity, the top of the TEOS layer on the non-patterned portion of the surface (the "TEOS reference plane") is close to horizontal with respect to the top of the Cu layer after the barrier layer polishing. Referring to FIG. 1D-1F, when the barrier layer polishing conditions have non-ideal Ta / TEOS and Cu / TEOS selectivity, a height difference occurs between the top of the TEOS layer on the non-patterned portion of the surface (the "TEOS reference plane") and the top of the Cu layer after the barrier layer polishing. This results in erosion, protrusion, and dishing.
[0139] In practice, a height difference typically occurs after Cu polishing, and the barrier polishing composition is evaluated for topography correction (nm). Thus, referring to FIG. 1F, if the height difference between the TEOS reference surface and the top of the Cu layer after the barrier layer polishing is smaller than the height difference before the barrier layer polishing, the topography is said to be corrected, and the topography correction (before (nm)-after (nm)) represents a positive value. Similarly, if the height difference between the TEOS reference surface and the top of the Cu layer after the barrier layer polishing is larger than the height difference before the barrier layer polishing, the topography correction (before (nm)-after (nm)) represents a negative value. Thus, the more "positive" or "negative" the topography correction (nm) is, the better a given polishing composition can correct (or avoid further deterioration of) non-ideal topography. On the other hand, the more "positive" or "negative" the topography correction (nm), the less effective a given polishing composition is at correcting (or avoiding further deterioration of) non-ideal topography. For purposes of this disclosure, a positive topography value (nm) represents that the top of the Cu layer is below the TEOS datum.
[0140] To evaluate the topography correction, the surface topography was measured using a Park Systems XE-120 AFM (Park Systems).
[0141] [Table 1]
[0142] [Example 2] Effect of phosphate surfactants on polishing performance To evaluate the effect of surfactant type and concentration on polishing performance, the polishing compositions shown in Table 2 were prepared according to the procedure described in Example 1, and their Ta, Cu, and TEOS removal rates, removal rate selectivities, and topography corrections were evaluated according to the methods disclosed in Example 1 above. Although the type and concentration of the phosphate surfactant were varied, all polishing compositions tested contained the following components at the following concentrations:
[0143] · 2.2 wt.% of abrasive 1 (see Table 1); ·KOH in an amount to adjust the pH to the desired value; 0.1% by weight of citric acid; 0.05% by weight of BTA; · 0.08% by weight of pullulan; 1.0% by weight of H2O2; and · 0.1% by weight of tripotassium citrate.
[0144] As mentioned above, the pH of the composition was adjusted by monitoring the pH while adding potassium hydroxide (KOH).
[0145] As shown in Table 2, the polishing compositions containing abrasive 1 (sulfonic acid modified silica; 30 nm) and polyoxyethylene (7) nonylphenyl phosphate (e.g., slurries 2-4, 16-17) or polyoxyethylene (10) nonylphenyl phosphate (e.g., slurry 8) showed excellent topography correction performance, Ta removal rate, Cu removal rate, TEOS removal rate, and Ta / TEOS selectivity. In particular, the slurries containing 0.01 wt% to 0.1 wt% polyoxyethylene (7) nonylphenyl phosphate showed maximum topography correction with favorable Cu removal rate and good Ta / TEOS removal rate selectivity, especially at pH values of 9 to 10.5 (see slurries 2-4 and 16-17).
[0146] [Table 2]
[0147] [Example 3] Effect of electrical conductivity control agents and water-soluble polymers on polishing performance To evaluate the effect of the type and concentration of EC control agent and the concentration of water-soluble polymer on polishing performance, the polishing compositions shown in Table 3 were prepared, and their Ta, Cu, and TEOS removal rates, removal rate selectivity, and topography correction were evaluated according to the method disclosed in Example 1 above. The type and concentration of EC control agent and the concentration of water-soluble polymer (pullulan) were varied. All polishing compositions tested contained the following components at the following concentrations.
[0148] 0.05% by weight of POE(7)-nonylphenyl phosphate; · 2.2 wt. % of abrasive 1 (see Table 1); 0.2% by weight of KOH; 0.1% by weight of citric acid; 0.05% by weight of BTA; and 1.0% H2O2 by weight.
[0149] As shown in Table 3, the polishing composition without water-soluble polymer shows insufficient topography correction, and the polishing composition containing 0.01 wt% to 0.08 wt% pullulan shows excellent topography correction (e.g., more than 30 nm) (see slurries 3, 21, 23, 24, and 26). The polishing composition containing the EC control agent at too low or too high concentration (e.g., 0 wt% or 1 wt%) shows insufficient topography correction (see slurries 22 and 25), and the polishing composition containing 0.03 wt% to 0.5 wt% tripotassium citrate as the EC control agent has excellent topography correction (e.g., more than 30 nm) (see slurries 3, 21, 23, and 24).
[0150] [Table 3]
[0151] [Example 4] Effect of abrasive type on polishing performance To evaluate the effect of abrasive type on polishing performance, the polishing compositions shown in Table 4 were prepared and their Ta, Cu, and TEOS removal rates, removal rate selectivities, and topography corrections were evaluated according to the method disclosed in Example 1 above. Although the abrasive types were varied, all abrasives were present at the same concentration (2.2 wt%). All polishing compositions tested had a pH of 10 and contained the following components at the following concentrations.
[0152] · 2.2 wt.% abrasive (see Table 4); 0.2% by weight of KOH; 0.1% by weight of citric acid; 0.05% by weight of BTA; · 0.08% by weight of pullulan; · 0.05% by weight of POE(7) nonylphenyl phosphate; 0.1% by weight of tripotassium citrate; and 1.0% H2O2 by weight.
[0153] As shown in Table 4, the polishing compositions containing abrasives 1, 3, 7, and 8 (slurries 3, 28, 32, and 33; having an average primary particle size of 30 nm or more) showed excellent topography correction, Cu removal rate, Ta removal rate, TEOS removal rate, and Ta / TEOS selectivity. On the other hand, abrasives 5 and 6 (slurries 30 and 31), having an average primary particle size of less than 30 nm, did not achieve good topography correction.
[0154] Furthermore, unmodified abrasives having an average primary particle size of 30 nm or more and a relatively broad particle size distribution (e.g., D90 / D10 ratio of greater than 1.3; see slurries 32 and 33) showed better polishing performance (topography correction, Cu removal rate, Ta removal rate, TEOS removal rate) than unmodified abrasives having an average primary particle size of 30 nm or more and a relatively narrow particle size distribution (e.g., D90 / D10 ratio of 1.4 or less; see slurries 27 and 29).
[0155] [Table 4]
[0156] While particular embodiments have been illustrated and described, it should be understood that changes and modifications can be made by those skilled in the art without departing from the technology in its broader aspects, as defined in the following claims.
[0157] The compositions and methods illustratively described herein may be suitably carried out in the absence of any element or limitation not specifically disclosed herein. Thus, for example, terms such as "comprising", "including", "containing" and the like are to be interpreted broadly and without limitation. Furthermore, the terms and expressions used herein are used as terms of description and not of limitation, and the use of such terms and expressions is not intended to exclude any equivalents of the features shown and described or portions thereof. It is recognized that various modifications are possible within the scope of the claimed disclosure. Thus, although the present disclosure has been specifically disclosed by preferred embodiments and optional features, it should be understood that modifications and variations of the disclosure disclosed and embodied herein may occur to those skilled in the art, and such modifications and variations are considered to be within the scope of the present invention.
[0158] The disclosure has been described broadly and generically herein. Each of the narrower species and subspecies groups that fall within the scope of the generic disclosure also form part of the method. This includes the generic description of the method with a proviso or negative limitation that excludes any subject matter from the genus, regardless of whether the exclusion is specifically recited herein. The technology is not limited in terms of the specific embodiments described in this application, which are intended as an illustration of one of the individual aspects of the technology. As will be apparent to those skilled in the art, many modifications and variations of the technology are possible without departing from the spirit and scope of the technology. In addition to those enumerated herein, functionally equivalent methods and devices within the scope of the technology will be apparent to those skilled in the art from the foregoing description. Such modifications and variations are intended to be within the scope of the technology. It should be understood that the technology is not limited to specific methods, reagents, compounds, compositions, or biological systems, which may of course vary. It should also be understood that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting.
[0159] Those skilled in the art will readily recognize that the present disclosure is fully adapted to carry out the subject matter and obtain the results and benefits described, as well as those inherent therein. Modifications and other uses of the present invention will occur to those skilled in the art. These modifications are encompassed within the spirit of the disclosure and are defined by the claims which define non-limiting embodiments of the disclosure.
[0160] Furthermore, where features or aspects of the disclosure are described in terms of a Markush group, those skilled in the art will recognize that the disclosure is thereby described in terms of any individual component or subgroup of components of the Markush group.
[0161] All documents, articles, publications, patents, patent publications, and patent applications cited herein are incorporated herein by reference in their entirety, except that the mention of any documents, articles, publications, patents, patent publications, and patent applications cited herein should not be construed as an admission or any form of suggestion that they constitute valid prior art or form part of the common general knowledge in any country in the world.
[0162] Other embodiments are defined in the following claims.
[0163] This application is based on U.S. Provisional Patent Application No. 63 / 540,817, filed September 27, 2023, the disclosure of which is incorporated by reference in its entirety into this specification.
Claims
1. an abrasive comprising silica particles having an average primary particle size of greater than 12 nm and / or having an average secondary particle size of greater than 30 nm; a phosphate surfactant; A water-soluble polymer; An electrical conductivity control agent; Including, the silica particles have a D90 / D50 ratio of greater than 1.3 or a D90 / D10 ratio of greater than 1.7 and / or are surface-modified with an organic acid; The phosphate surfactant has 15 or less oxyethylene units and linear or branched C 4 and the above alkylphenyl, and is present at a concentration of less than 0.5 wt.% based on the total weight of the polishing composition; the electrical conductivity control agent is present at a concentration of less than 1 wt. %, based on the total weight of the polishing composition; The pH is greater than 8 and less than 11. Polishing composition.
2. 10. The polishing composition of claim 1, wherein the phosphate surfactant is present at a concentration of greater than 0.01 wt.%, based on the total weight of the polishing composition.
3. The polishing composition according to claim 1 , wherein the water-soluble polymer comprises a polysaccharide.
4. The polishing composition according to claim 3 , wherein the polysaccharide comprises pullulan.
5. The polishing composition according to claim 1 , wherein the electrical conductivity control agent comprises a citrate salt.
6. The polishing composition according to claim 5 , wherein the citrate is at least one of tripotassium citrate and diammonium citrate.
7. 2. The polishing composition of claim 1, wherein the electrical conductivity control agent is present at a concentration of greater than 0.03 wt. %, based on the total weight of the polishing composition.
8. The phosphate surfactant has the following formula (I): [Tail - (OC 2 H 5 ) n -O] m -PO q H r (I) During the ceremony, O.C. 2 H 5 is an oxyethylene unit, n is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15; (m, q, r) is (1, 3, 2), (2, 2, 1), or (3, 1, 0); The tail is C 4 or more alkylphenyl. The polishing composition according to claim 1 , wherein
9. and / or the tail is C 5 ~C 11 The polishing composition according to claim 8 , wherein the alkylphenyl is an alkylphenyl group.
10. the phosphate surfactant is present in a concentration of greater than 0.01 wt.%, based on the total weight of the polishing composition; the electrical conductivity control agent is present at a concentration of greater than 0.03 wt. %, based on the total weight of the polishing composition; 10. The polishing composition of claim 9, wherein the silica particles have an average primary particle size of less than 78 nm and, when not surface-modified with an organic acid, have a D90 / D50 ratio of less than 1.
9.
11. 11. The polishing composition of claim 10, wherein the phosphate surfactant is present at a concentration of less than 0.1 wt%, based on the total weight of the polishing composition.
12. 11. The polishing composition of claim 10, wherein the electrical conductivity control agent is present at a concentration of less than 0.5 wt. %, based on the total weight of the polishing composition.
13. The polishing composition of claim 10 , wherein the water-soluble polymer is present at a concentration of greater than 0.01 wt %, based on the total weight of the polishing composition.